Wettable Silicone Hydrogel Contact Lenses
Patent Information
- Application Number
- JP2023198110
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-16
- Filing Date
- 2023-11-22
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2040-12-15
Smart Images

Figure 0007629074000095 
Figure 0007629074000096 
Figure 0007629074000097
Abstract
Description
[Technical field]
[0001] The present invention relates generally to silicone hydrogel contact lenses having enhanced and sustained wettability, and methods for making same. [Background technology]
[0002] Silicone hydrogel (SiHy) contact lenses, made from hydrated cross-linked polymer-based materials that contain silicone and a certain amount of water in the lens polymer matrix at equilibrium, are becoming increasingly popular because of their high oxygen permeability, which minimizes adverse effects on corneal health. However, silicone is hydrophobic and has a strong tendency to migrate to the lens surface exposed to air, so incorporating silicone into contact lens materials can have an undesirable effect on the hydrophilicity and wettability of SiHy contact lenses. Contact lens manufacturers have made great efforts to develop SiHy contact lenses with hydrophilic and wettable surfaces.
[0003] One class of approaches to modify the hydrophilicity and wettability of SiHy contact lenses is to subject the SiHy contact lenses to post-molding surface treatments. Examples of post-molding surface treatments include plasma treatments (see, e.g., commercially available lenses AIR OPTIX® from Alcon, PremiO™ from Menicon, and PUREVISION™ from Bausch & Lomb); covalent attachment of hydrophilic polymers to the SiHy contact lenses by various mechanisms (see, e.g., U.S. Pat. Nos. 6,099,122, 6,436,481, 6,440,571, 6,447,920, 6,462, 6,622, 6,646 ... Nos. 5,056, 6,521,352, 6,586,038, 6,623,747, 6,730,366, 6,734,321, 6,835,410, 6,878,399, 6,923,978, 6,440,571, and 6,500,481, and U.S. Patent Application Publication No. 2009 / 014 5086 A1, 2009 / 0145091 A1, 2008 / 0142038 A1, and 2007 / 0122540 A1; layer-by-layer (LbL) polyionic material deposition techniques (see, e.g., U.S. Pat. Nos. 6,451,871, 6,719,929, 6,793,973, 6,884,457, Nos. 6,896,926, 6,926,965, 6,940,580, 7,297,725, 8,044,112, 7,858,000, and 8,158,192); crosslinking of LbL coatings on SiHy contact lenses (see, e.g., U.S. Pat. Nos. 8,147,897 and 8,142,835);and application of non-silicone hydrogel coatings to SiHy contact lenses (see, e.g., U.S. Pat. Nos. 8,480,227, 8,529,057, 8,939,577, 8,944,592, 9,239,409, 9,244,200, 9,411,171, 9,505,184, 9,507,173, 9,738,813, 9,816,009, 1,013,1815, 1,022,509, and 1,0308,835; and U.S. Patent Application Publication Nos. 2019 / 0055427, 2019 / 0179055, and 2019 / 0309188). ;
[0004] One different approach is described in U.S. Pat. Nos. 6,867,245, 7,268,198, 7,540,609, 7,572,841, 7,750,079, 7,934,830, 8,231,218, 8,367,746, 8,445,614, 8,481,662, 8,487,058, 8,513,325, 8,703,891, 8,750,100, and 8,934,830. Specification No. 8820928, Specification No. 8865789, Specification No. 8937110, Specification No. 8937111, Specification No. 9057821, Specification No. 9057822, Specification No. 9121998, Specification No. Specification No. 9,125,808, Specification No. 9140825, Specification No. 9140908, Specification No. 9156934, Specification No. 9164298, Specification No. 9170349, Specification No. 9188702 , 9217813, 9296159, 9322959, 9322960, 9360594, 9529119, 6,367,929, 6,822,016, 7,052,131, and 7,249,848, and published U.S. applications (e.g., 2018-0355112 and 2018-035656 As proposed in US Pat. No. 2, a monomeric wetting agent (e.g., N-vinylpyrrolidone, N-vinyl-N-methylacetamide, etc.) or a high molecular weight hydrophilic polymer (e.g., polyvinylpyrrolidone with Mw≧100,000 Daltons for interpenetrating network formation) is incorporated into the lens formulation to produce naturally wettable SiHy contact lenses (i.e., wettable SiHy lenses without post-molding surface treatment). Biofinity® (CooperVision, Dk=128 barrer, 48% H 2 O), Avaira (registered trademark) (CooperVision, Dk=100 barrer, 46%H 2 O), Clariti® (CooperVision, Dk=60barrer, 56%H 2O), MyDay (registered trademark) (CooperVision, Dk=80barrer, 54%H 2 O), ULTRA (trademark) (Bausch&Lomb, Dk=114barrer, 46%H 2 O), Acuvue® Oasys® (Johnson & Johnson, Dk approx. 105 barrer, 38% H 2 O); Acuvue® Advance® (Johnson & Johnson, Dk approx. 65 Barrer, 47% H 2 O); Acuvue® TruEye™ (Johnson & Johnson, Dk approx. 100 Barrer, 46% H 2 This approach can be utilized in the manufacturing process of commercial SiHy lenses such as 1,2-dichlorophenyl ether (1,2,3-trifluoroethylene) to provide fresh (unused) SiHy lenses with a sufficiently hydrophilic surface. Although this approach can be used in the manufacture of commercial SiHy lenses to provide fresh (unused) SiHy lenses with a sufficiently hydrophilic surface, it has several limitations, such as slightly higher haze due to incompatibility of the polymerizable silicone component with the monomeric wetting agent and other hydrophilic components; higher surface silicone content; susceptibility to dry spots and / or hydrophobic surface areas formed due to partial failure to prevent air exposure, dehydration-rehydration cycles, eyelid shear forces, silicone migration to the surface, and / or exposure of the silicone; and poor lubricity.
[0005] US Patent No. 9829723 discloses an improved contact lens product, which comprises a plasma-coated silicone hydrogel contact lens, which is immersed in a packaging solution and autoclaved, comprising a polyoxyethylene-polyoxybutylene block copolymer and a high molecular weight copolymer of N-vinylpyrrolidone and at least one amino-containing vinyl monomer. According to this patent, during autoclaving of the plasma-coated silicone hydrogel contact lens, which is immersed in a buffered saline solution containing a relatively high concentration (for example, 400 ppm used in the examples) of the copolymer of N-vinylpyrrolidone and amino-containing vinyl monomer and the polyoxyethylene-polyoxybutylene block copolymer, a relatively stable film can be formed on the plasma-coated silicone hydrogel contact lens, providing improved and sustainable wettability of the resulting plasma-coated silicone hydrogel contact lens.
[0006] Thus, there is a need for coating-free silicone hydrogel contact lenses that have improved and sustained surface wettability and are suitable for continuous wear for seven days, and an efficient method for producing such silicone hydrogel contact lenses. Summary of the Invention [Means for solving the problem]
[0007] In one aspect, the present invention provides an ophthalmic product comprising a sealed, autoclave-sterilized package comprising a post-autoclaved packaging solution and a ready-to-use silicone hydrogel contact lens immersed therein, wherein the post-autoclaved packaging solution is a buffered saline solution having a pH of about 6.0 to about 8.0 and comprises a polymeric surfactant, the polymeric surfactant comprising at least one hydrophilic poly(oxyethylene) segment and at least one hydrophobic poly(oxybutylene) segment and having an HLB (hydrophilic-lipophilic balance) value of about 11 to about 16 and a number average molecular weight of about 800 to about 20,000 Daltons, and the ready-to-use silicone hydrogel contact lens comprises a preformed silicone hydrogel contact lens immersed in the pre-autoclaved packaging solution comprising the polymeric surfactant within the package. and a ready-to-use silicone hydrogel contact lens, which is obtained by placing a ready-to-use silicone hydrogel contact lens in a sealed package, sealing and autoclaving the lens, the ready-to-use silicone hydrogel contact lens comprising a polymeric surfactant physically distributed within the polymer matrix of the ready-to-use silicone hydrogel contact lens as evidenced by the ability to release the polymeric surfactant in an amount of at least 0.2 μg / lens / 24 hours as measured in an aqueous extraction process consisting of seven cycles of simulated one-day-wear extraction, the ability to release the polymeric surfactant being the amount of polymeric surfactant released per lens over a 24-hour period in the extraction medium used in the last cycle of the seven cycles of simulated one-day-wear extraction, the ready-to-use silicone hydrogel contact lens having a first static water contact angle of about 75° or less as measured by the Sessile Drop Method directly from the sealed package, WCA. OOP and a second static water contact angle of approximately 85° or less, measured by the sessile drop method immediately after seven cycles of simulated one-day wear extraction, WCA 7_S1DW and further has an oxygen permeability of at least 50 barrer, an elastic modulus of about 0.2 MPa to about 1.5 MPa, and an equilibrium moisture content of about 38% to about 80% by weight.
[0008] In another aspect, the present invention provides a method for producing an ophthalmic product, the method comprising the steps of: a) sealing a preformed silicone hydrogel contact lens in a container containing a pre-autoclaved packaging solution to form a sealed package, the preformed silicone hydrogel contact lens being free of a coating and having an oxygen permeability of at least 50 barrer, an elastic modulus of about 0.2 MPa to about 1.5 MPa, and an equilibrium water content of about 38% to about 80% by weight, the pre-autoclaved packaging solution being a buffered saline solution having a pH of about 6.0 to about 8.0, and comprising a polymeric surfactant, the polymeric surfactant comprising at least one hydrophilic poly(oxyethylene) segment and at least one hydrophobic poly(oxybutylene) segment, having an HLB value of about 11 to about 16, and a number average molecular weight of about 800 to about 20,000 Daltons; and and b) autoclaving the sealed package containing the preformed silicone hydrogel contact lens therein for at least about 30 minutes to obtain an ophthalmic product, the ophthalmic product comprising a ready-to-use silicone hydrogel contact lens in the sealed and autoclaved package, the ready-to-use silicone hydrogel contact lens comprising a polymeric surfactant physically distributed within a polymer matrix of the ready-to-use silicone hydrogel contact lens as evidenced by having an ability to release the polymeric surfactant in an amount of at least 0.2 μg / lens / 24 hours as measured in an aqueous extraction process consisting of seven cycles of simulated daily wear extraction, and having a first static water contact angle of about 75° or less as measured by the Sessile Drop Method directly removed from the sealed package, WCA. OOP and a second static water contact angle of approximately 85° or less, measured by the sessile drop method immediately after seven cycles of simulated one-day wear extraction, WCA 7_S1DW and wherein the polymeric surfactant release capacity is the amount of polymeric surfactant released per lens over 24 hours into the extraction medium used in the last cycle of 7 cycles of simulated daily wear extraction.
[0009] These and other aspects of the present invention will become apparent from the following description of the presently preferred embodiments. The following detailed description is merely exemplary in nature and is not intended to limit the scope of the invention, as defined by the appended claims, and equivalents thereof. [Brief description of the drawings]
[0010] [Figure 1] 1 is an outline of a method for measuring the water-drying time of contact lenses. [Diagram 2] These are common dimensions for contact lenses. [Figure 3A] 1 is a cross-sectional fluorescence image of a ready-to-use SiHy lens that has been packaged in a packaging solution containing a polymeric surfactant and autoclaved, according to a preferred embodiment of the present invention. [Figure 3B] FIG. 3B is a confocal microscopy line scan of a cross section along the line shown in FIG. 3A. [Figure 4A] FIG. 3B is a fluorescent image of a cross section of a SiHy lens packaged in the same packaging solution used in FIG. 3A, but not autoclaved. [Figure 4B] 4B is a confocal microscopy line scan of a cross section along the line shown in FIG. 4A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs. In general, the nomenclature and laboratory procedures used herein are known and commonly employed by those skilled in the art. These procedures use conventional methods, such as those performed by those skilled in the art and commonly referred to in various ways. Where a term is given in the singular, the inventors also contemplate the plural form of that term. The nomenclature used herein and the laboratory procedures described below are known and commonly employed in the art.
[0012] In this application, the abbreviation "SiHy" means silicone hydrogel; the abbreviation "EO" means oxyethylene-C 2 H 4 O-; the abbreviation "BO" stands for oxybutylene-C 4 H 8 O-; the abbreviations "PEO," "PBO," and "PEO" mean poly(oxyethylene), poly(oxybutylene), and poly(oxyethylene), respectively; the abbreviation "PEG" means polyethylene glycol.
[0013] In this application, the term "about" as used herein means that the number referred to as "about" includes the stated number plus or minus 1 to 10% of the stated number.
[0014] "Contact lens" refers to a structure that can be placed on or in the eye of a wearer. A contact lens can, but need not, correct, improve or alter the user's vision. Contact lenses can be of any suitable material known in the art or later developed, and they can be hard lenses, rigid gas permeable lenses, soft lenses or hybrid lenses.
[0015] "Soft contact lens" refers to a contact lens that has a modulus of elasticity (ie, Young's modulus) of less than 2.5 MPa.
[0016] "Hydrogel" or "hydrogel-based material" refers to a crosslinked polymer-based material that has a three-dimensional polymer network (i.e., polymer matrix) and is insoluble in water but can retain at least 10 weight percent water in its polymer matrix when fully hydrated.
[0017] The terms "silicone hydrogel" or "SiHy" used in this application are interchangeable and refer to a hydrogel containing silicone. Silicone hydrogel (SiHy) is typically obtained by copolymerization of a polymerizable composition containing at least one silicone-containing vinyl monomer, or at least one silicone-containing vinyl macromer, or at least one silicone-containing prepolymer having ethylenically unsaturated groups.
[0018] As used in this application, the terms "non-silicone hydrogel" or "non-SiHy" are interchangeable and refer to hydrogels that are theoretically free of silicon.
[0019] Siloxane, often also called silicone, refers to a molecule having a -Si-O-Si- moiety, or at least one -Si-O-Si- moiety, where each Si atom has two organic groups as substituents.
[0020] As used in this application, "ready-to-use SiHy contact lenses" refers to fully hydrated, autoclave sterilized SiHy contact lenses that are ready for direct patient use.
[0021] "Hydrophilic," as used herein, describes a material or portion thereof that tends to associate with water rather than with lipids.
[0022] "Vinyl monomer" refers to a compound that has one and only one ethylenically unsaturated group, is soluble in a solvent, and can be polymerized chemically or thermally.
[0023] As used in this application, the term "ethylenically unsaturated group" is used broadly herein and is intended to encompass any group that contains at least one >C=C< group. Exemplary ethylenically unsaturated groups include, but are not limited to, (meth)acryloyl [ka] , allyl, vinyl, styrenyl, or other C=C containing groups.
[0024] The term "terminal (meth)acryloyl group" refers to one (meth)acryloyl group at one of the two ends of the main chain (or backbone) of an organic compound, as known to those skilled in the art.
[0025] The term "(meth)acrylamide" refers to methacrylamide and / or acrylamide.
[0026] The term "(meth)acrylate" refers to methacrylate and / or acrylate.
[0027] As used herein, "chemically" with respect to curing, crosslinking or polymerization of a polymerizable composition, prepolymer or material means that the curing (e.g., crosslinking and / or polymerization) is effected by actinic radiation, such as, for example, UV / visible radiation, ionizing radiation (e.g., gamma or X-ray radiation), microwave radiation, etc. Methods of thermal or chemical curing are well known to those skilled in the art.
[0028] As used herein, "hydrophilic vinyl monomer" refers to a vinyl monomer that, as a homopolymer, typically yields a polymer that is water soluble or capable of absorbing at least 10 weight percent water.
[0029] As used herein, "hydrophobic vinyl monomer" refers to a vinyl monomer that, as a homopolymer, typically results in a polymer that is water insoluble or can absorb less than 10 weight percent water.
[0030] "Blended vinyl monomer" refers to a vinyl monomer that is capable of dissolving both the hydrophilic and hydrophobic components of the polymerizable composition to form a solution.
[0031] The term "acrylic monomer" refers to a vinyl-based monomer having one single (meth)acryloyl group.
[0032] "N-vinyl amide monomer" means a monomer in which a vinyl group is bonded directly to the nitrogen atom of an amide group. [ka] It refers to an amide compound having the formula:
[0033] "Macromer" or "prepolymer" refers to a compound or polymer that contains ethylenically unsaturated groups and has a number average molecular weight greater than 700 Daltons.
[0034] The term "vinyl crosslinker" as used in this application refers to an organic compound having at least two ethylenically unsaturated groups. "Vinyl crosslinker" refers to a vinyl crosslinker having a molecular weight of 700 Daltons or less.
[0035] As used in this application, the term "polymer" means a material formed by polymerizing / crosslinking one or more monomers, or macromers, or prepolymers, or combinations thereof.
[0036] The term "molecular weight" of a polymeric material (including monomeric or macromeric materials) as used in this application refers to number average molecular weight unless otherwise specified or different test conditions are indicated. Those skilled in the art will recognize that molecular weight can be determined by known methods, such as GPC (gel permeation chromatography) equipped with one or more of a refractive index detector, a low angle laser light scattering detector, a multi-angle laser light scattering detector, a differential viscometry detector, a UV detector, and an infrared (IR) detector; MALDI-TOF MS (matrix-assisted desorption / ionization time-of-flight mass spectrometry); 1 Recognize methods to determine the molecular weight of polymers, such as according to H NMR (proton nuclear magnetic resonance) spectroscopy.
[0037] The "polysiloxane segment" is represented by the following formula: [ka] (In the formula, R 1 ' and R 2 ' is C 1 ~C 10 Alkyl, C 1 ~C 4 Alkyl- or C 1 ~C 4 -alkoxy substituted phenyl, C 1 ~C 10 Fluoroalkyl, C 1 ~C 10 Fluoroether, C 6 ~C 18 Aryl radical, -alk-(OC 2 H 4 ) γ1 -OR o (In the formula, alk is C 1 ~C 6 is an alkyl diradical, R o is H or C 1 ~C 4 alkyl, and γ1 is an integer from 1 to 10; 2 ~C 40 Organic radicals are hydroxyl (-OH), carboxyl (-COOH), and -NR 3 'R 4 ',-NR 3 '-amino bond, -CONR 3 '-amide bond, -CONR 3 'R 4 ' amide, -OCONH- urethane bond, and C 1 ~C 4 R has at least one functional group selected from the group consisting of alkoxy groups; 3 ' and R 4 ' are each independently hydrogen or C 1 ~C 15 (It is alkyl) "siloxane" refers to a polymer chain consisting of at least three consecutively and directly bonded siloxane units (divalent radicals), each of which is independent of the other, having the formula:
[0038] "Polysiloxane vinyl crosslinker" refers to a compound that contains at least one polysiloxane segment and at least two ethylenically unsaturated groups.
[0039] "Linear polysiloxane vinyl crosslinker" refers to a compound that includes a backbone that contains at least one polysiloxane segment and that is terminated with one ethylenically unsaturated group at each of the two ends of the backbone.
[0040] "Chain-extended polysiloxane vinyl crosslinker" refers to a compound that contains at least two ethylenically unsaturated groups and at least two polysiloxane segments, each pair of which is linked by a divalent radical.
[0041] The term "alkyl" refers to a monovalent radical obtained by removing a hydrogen atom from a straight-chain or branched alkane compound. An alkyl group (radical) forms one bond with one other group in an organic compound.
[0042] The terms "alkylene divalent group," "alkylene diradical," or "alkyl diradical" are interchangeable and refer to a divalent radical obtained by removing one hydrogen atom from an alkyl. An alkylene divalent group forms two bonds with other groups in an organic compound.
[0043] The terms "alkoxy" or "alkoxyl" refer to a monovalent radical obtained by removing a hydrogen atom from the hydroxyl group of a straight-chain or branched alkyl alcohol. An alkoxy group (radical) forms one bond with one other group in an organic compound.
[0044] The term "amino group" as used herein refers to a primary or secondary amino group of formula -NHR', where R' is hydrogen or C, unless otherwise specified. 1 ~C 20 It refers to an unsubstituted or substituted straight-chain or branched alkyl group.
[0045] In this application, the term "substituted" with respect to an alkyl diradical or alkyl radical means that the alkyl diradical or alkyl radical contains at least one substituent replacing one hydrogen atom of the alkyl diradical or alkyl radical, which can be hydroxy (-OH), carboxy (-COOH), -NH 2 , sulfhydryl (-SH), C 1 ~C 4 Alkyl, C 1 ~C 4 Alkoxy, C 1 ~C 4 Alkylthio(alkyl sulfide), C 1 ~C 4 Acylamino, C 1 ~C 4 Alkylamino, Di-C 1 ~C 4 alkylamino, alkylamino, and combinations thereof.
[0046] The term "phosphorylcholine" as used in this application means [ka] (In the formula, n is an integer of 1 to 5, and R 1 , R 2 and R 3 are independent of each other, C 1 ~C 8 Alkyl or C 1 ~C 8 hydroxyalkyl) This refers to a zwitterionic group.
[0047] A free radical initiator can be either a photoinitiator or a thermal initiator. A "photoinitiator" refers to a chemical that initiates a free radical crosslinking / polymerization reaction by using light. A "thermal initiator" refers to a chemical that initiates a radical crosslinking / polymerization reaction by using thermal energy.
[0048] The inherent "oxygen permeability" of a material, Dk iis the rate at which oxygen passes through the material. As used in this application, the term "oxygen permeability (Dk)" in reference to hydrogels (silicone or non-silicone) or contact lenses refers to the corrected oxygen permeability (Dk c ), which is measured at approximately 34-35 °C and corrected for the surface resistance to oxygen flux caused by boundary layer effects, according to the procedure described in ISO 18369-4. Oxygen permeability is usually expressed in units of barrer, where "barrer" is the unit [(cm 3 oxygen)(mm) / (cm 2 )(sec)(mmHg)]×10 -9 It is defined as:
[0049] The "oxygen permeability" of a lens or material, Dk / t, is the rate at which oxygen passes through a particular lens or material of average thickness t [in mm] over the area being measured. Oxygen permeability is usually expressed in units of barrer / mm, where "barrer / mm" is the unit of [(cm 3 oxygen) / (cm 2 )(sec)(mmHg)]×10 -9 It is defined as:
[0050] As used herein, "ophthalmically compatible" refers to a material or surface of a material that can be in intimate contact with the ocular environment for extended periods of time without causing significant damage to the ocular environment and without causing significant discomfort to the user.
[0051] The term "modulus" or "elastic modulus" with respect to a contact lens or material means the tensile modulus, or Young's modulus, which is a measure of the stiffness of a contact lens or material under tension. Those skilled in the art are well aware of how to determine the elastic modulus of a SiHy material or contact lens, preferably by following the procedure described in Example 1.
[0052] HLB stands for the hydrophilic-lipophilic balance (HLB) of an amphiphilic molecule, and its value is obtained by dividing the weight percentage of the hydrophilic moieties by five.
[0053] In this application, "seven cycles of simulated one-day-wear extraction" or "seven cycles of S1DW extraction" are interchangeable and refer to (a) removing and wiping one to three ready-to-use SiHy contact lenses from their sealed packages, and (b) soaking the wiped ready-to-use SiHy contact lenses in 1.0 mL of fresh phosphate buffered saline (PBS) (pH 7.2±0.2 at 25° C., approximately 0.076% by weight NaH 2 PO 4 H 2 O, about 0.31% by weight of Na 2 HPO 4 2H 2 % n-hexane and about 0.77 wt. % n-NaCl) at 35° C. for 24 hours with stirring, pipetting out all of the PBS used in the first cycle of S1DW extraction from the vial, and analyzing the pipetted PBS used in the first cycle of S1DW extraction; and (b) cycles 2-7 of S1DW extraction, which respectively include adding 1.0 mL of fresh PBS as an extraction medium into a vial containing a ready-to-use SiHy contact lens that has been subjected to a preceding cycle of S1DW extraction, immersing the ready-to-use SiHy contact lens in the added 1 mL of fresh PBS as an extraction medium at 35° C. for 24 hours with stirring, pipetting out all of the PBS used in the current cycle of S1DW extraction from the vial, and analyzing the pipetted PBS used in the current cycle of S1DW extraction. Each extraction medium used in each of the seven cycles of S1DW extraction can be analyzed by any method known to one of skill in the art, preferably by UPLC methods.
[0054] According to the present invention, the step of soaking one ready-to-use SiHy contact lens in 1.0 mL of fresh PBS at 35° C. for 24 hours is intended to simulate a patient wearing the ready-to-use SiHy lens on his eye for one day (8-24 hours). It should be pointed out that the amount of fresh PBS in each cycle is selected to correspond to the normal average tear production by the eye per day. Schirmer, in his classic study on tear secretion in 1903, estimated the amount of tears produced in a 16-hour waking period under basic circumstances to be 0.5-0.75 grams (Schirmer, O. Graefes Arhiv für Ophthalmologie 1903,56:197-291).
[0055] It is understood that the number of ready-to-use SiHy contact lenses used in the seven cycles of the simulated daily wear extraction study will depend on the detection limit of the analytical method selected (e.g., UPLC) and the amount of polymeric surfactant leached per lens per 24 hours. As known to those skilled in the art, a greater number of ready-to-use SiHy contact lenses can be used in the seven cycles of the simulated daily wear extraction study to increase the accuracy and reliability of the test.
[0056] "UVA" refers to radiation occurring at wavelengths between 315 and 380 nanometers; "UVB" refers to radiation occurring in the range of 280 to 315 nanometers; and "violet" refers to radiation occurring at wavelengths between 380 and 440 nanometers.
[0057] "UVA Transmittance" (or "UVA%T"), "UVB Transmittance" or "UVB%T", and "Violet Transmittance" or "Violet %T" are calculated according to the following formulas: UVA%T=315nm~380nm average % transmittance x 100 UVB%T=280nm~315nm average % transmittance x 100 Violet%T=380nm~440nm average % transmittance x 100
[0058] The terms "essentially wettable" and "naturally wettable" with respect to SiHy contact lenses are interchangeable and refer to the properties of the SiHy contact lens that, after a SiHy contact lens is formed by thermally or chemically polymerizing (i.e., curing) a SiHy lens formulation, the SiH has a water break-off time (WBUT) of about 5 seconds or more and a static sessile drop water contact angle (WCA) of about 90° or less without any surface treatment. s According to the present invention, the WBUT and the WCA s is measured according to the procedure described in Example 1.
[0059] "Coating" in reference to a contact lens means that the contact lens has a thin layer on its surface of a material that is different from the bulk material of the contact lens and that is obtained by subjecting the contact lens to a surface treatment.
[0060] As used herein, "surface modification" or "surface treatment" means that an article has been treated with a surface treatment process in which (1) a coating is provided on the surface of the article, (2) a chemical species is adsorbed onto the surface of the article, (3) the chemical nature (e.g., electrostatic charge) of chemical groups on the surface of the article is altered, or (4) the surface properties of the article are otherwise altered. Exemplary surface treatment processes include, but are not limited to, surface treatment with energy (e.g., plasma, electrostatic charge, irradiation or other energy sources), chemical treatment, grafting of hydrophilic vinyl monomers or macromers onto the surface of the article, mold transfer coating as disclosed in U.S. Pat. No. 6,719,929, incorporation of wetting agents into lens formulations to make contact lenses as proposed in U.S. Pat. Nos. 6,367,929 and 6,822,016, reinforced mold transfer coating as disclosed in U.S. Pat. No. 7,858,000, and hydrophilic coating by covalent bonding or physical deposition of one or more layers of one or more hydrophilic polymers onto the contact lens surface as disclosed in U.S. Pat. Nos. 8,147,897 and 8,409,599, and U.S. Patent Publication Nos. 2011 / 0134387, 2012 / 0026457, and 2013 / 0118127.
[0061] "Post-cure surface treatment," with respect to SiHy contact lenses, refers to a surface treatment process that occurs after a SiHy contact lens is formed by curing (i.e., thermally or chemically polymerizing) a SiHy lens formulation. "SiHy lens formulation" refers to a polymerizable composition that contains all of the polymerizable components necessary to produce a SiHy contact lens or SiHy lens bulk material, as is known to those skilled in the art.
[0062] The present invention generally relates to an ophthalmic product comprising a sealed, autoclaved sterilized lens package comprising a packaging solution and a ready-to-use SiHy contact lens immersed in the packaging solution. The packaging solution comprises a polymeric surfactant having an HLB value of about 11 to about 16 and a number average molecular weight of about 800 to about 20,000 Daltons. The ready-to-use SiHy contact lens comprises such a polymeric surfactant thereon (i.e., surface-bound or surface-adsorbed polymeric surfactant), providing excellent wettability to the ready-to-use SiHy contact lens directly removed from the lens package. It is believed that at least a significant portion of the polymeric surfactant adsorbed to the lens surface may be released into the tear fluid of the eye immediately after insertion into the eye. Considering that the normal average tear volume is 6.2±2.0 μL (S. Mishima et al., Invest. Ophthalmol. Vis. Sci. 1966, 5:264-276), the concentration of the polymeric surfactant in the tear fluid may be very high immediately after the lens is inserted into the eye, providing excellent wettability to the eye. The ready-to-use SiHy contact lens also contains a leachable polymeric surfactant that is physically taken up (absorbed) by the SiHy contact lens during autoclaving and physically distributed in the polymer matrix of the SiHy contact lens. The polymeric surfactant physically absorbed and distributed in the ready-to-use SiHy contact lens is released to the patient's eye for at least seven days of daily wear, replenishing the polymeric surfactant that binds to the surface of the lens, thereby providing sustainable wettability to the contact lens and eye. A ready-to-use SiHy contact lens with these two functions can provide a comfortable fit to the patient for at least one week of wear. Thus, the SiHy contact lens of the present invention is suitable for use as a weekly disposable contact lens.
[0063] The present invention is based in part on the surprising discovery that SiHy contact lenses having a relatively high equilibrium water content (at least 38%, preferably at least 40%), a relatively low modulus (e.g., less than 1.5 MPa), and a relatively high oxygen permeability (e.g., at least 50 Barrer), and no coatings thereon, can be provided with the two desirable characteristics noted above by simply packaging the SiHy contact lenses in a lens package containing a polymeric surfactant and autoclaving the polymeric surfactant, the polymeric surfactant being comprised of at least one hydrophilic poly(oxyethylene) segment and at least one hydrophobic poly(oxybutylene) segment, having an HLB value of from about 11 to about 16 and a number average molecular weight of from about 800 to about 20,000 Daltons, and present in the lens packaging solution in an amount low enough not to significantly increase the diameter of the lens, yet sufficient to provide the SiHy contact lenses with the two desirable characteristics.
[0064] It is believed that if a SiHy contact lens has an oxygen permeability of at least 50 barrers, it may have hydrophobic (i.e., silicone) regions intermingled with hydrophilic regions on a microscopic scale. The number of such microscopic hydrophobic regions will be large enough to dissolve a large amount of a polymeric surfactant having an HLB value of about 11 to about 16.
[0065] It is also believed that when a SiHy contact lens has an elastic modulus of about 0.2 MPa to about 1.5 MPa and an equilibrium water content of about 38% to about 80% by weight, it can have pores of a size large enough for a sufficient amount of a polymeric surfactant having a number average molecular weight of about 800 to about 20,000 Daltons to penetrate into the interior of the SiHy contact lens during autoclaving and storage, and thereafter leach out of the SiHy contact lens when worn on the eye.
[0066] Furthermore, it is believed that the unique inherent amphiphilicity of the polymeric surfactant of the present invention allows it to be physically attached to the surface of the SiHy contact lens described above and physically distributed within the polymer matrix of the SiHy contact lens described above. The hydrophobic poly(oxybutylene) segments of the polymeric surfactant can have hydrophobic interactions with the silicone patches on the lens surface and the silicone just below the surface as well as with the microscopic hydrophobic regions inside the SiHy contact lens. Such hydrophobic-hydrophobic interactions provide the driving force for the polymeric surfactant to physically bind to the lens surface (form a surface layer) and penetrate the lens. Furthermore, it is believed that the polymeric surfactant, due to its amphiphilic nature, is located at the interface between the microscopic hydrophobic and hydrophilic regions to minimize surface energy, thereby reducing the migration rate of the polymeric surfactant from the interior of the SiHy contact lens to the eye environment during wear.
[0067] Typically, contact lenses that are hydrated and packaged in a packaging solution must be sterilized before being provided to a patient. Sterilization of hydrated lenses during manufacture and packaging is typically accomplished by autoclaving. The autoclaving process involves heating the contact lens package to a temperature of about 118°C to about 125°C for about 20 to 50 minutes under pressure. It has been found that during autoclaving, such polymeric surfactants present in the packaging solution can not only physically adhere to the surface of the SiHy contact lens, but can also penetrate deep into the SiHy contact lens so as to be distributed within the polymer matrix of the SiHy contact lens. The efficiency of penetration of the polymeric surfactant into the SiHy contact lens described above during autoclaving will be high enough to reduce the concentration of the polymeric surfactant in the lens packaging solution while still retaining a sufficient amount of leachable polymeric surfactant entrapped that can be released to the patient's eye to provide the contact lens with sustainable wettability for at least 7 days of daily wear.
[0068] It is known that hydrophobic interactions (forces) are strongly dependent on temperature, and the higher the temperature, the stronger the hydrophobic-hydrophobic interactions and the stronger the driving force for the polymeric surfactant to penetrate (diffuse) into the SiHy contact lens. It is believed that the penetration of the polymeric surfactant present in the packaging solution into the SiHy contact lens is greatly accelerated during autoclaving, and as a result, a large amount of the polymeric surfactant can be incorporated into the SiHy contact lens.
[0069] It should be pointed out that although the autoclave process can accelerate the penetration process of the polymeric surfactant, it may still not be enough for the polymeric surfactant to achieve distribution equilibrium between the packaging solution and the silicone hydrogel contact lens. During storage at room temperature of the sealed and autoclaved lens package containing the ready-to-use SiHy contact lens therein, the amount of polymeric surfactant taken up by the silicone hydrogel contact lens is likely to increase over time until equilibrium is reached. Such a slow post-autoclave uptake process of the polymeric surfactant by the silicone hydrogel contact lens immersed in the packaging solution in the sealed lens package will ensure that a larger amount of the polymeric surfactant is taken up by the silicone hydrogel contact lens, and then released when worn on the eye.
[0070] It should also be pointed out that the SiHy contact lenses of the present invention cannot be prepared from SiHy lens formulations that include polymeric surfactants having number average molecular weights of about 800 to about 20,000 Daltons, since it is highly likely that the polymeric surfactant will be removed from the resulting SiHy contact lens during the lens extraction and hydration processes required for the manufacture of SiHy contact lenses.
[0071] By using the method of the present invention, the adsorption of polymeric surfactant to the lens surface and incorporation of polymeric surfactant into the lens can be combined with a sterilization step (autoclaving) in the manufacture of SiHy contact lenses. The resulting contact lenses can have not only a combination of desirable contact lens properties such as relatively high oxygen permeability, relatively high water content, relatively low modulus, and good surface wettability, but also the two characteristics mentioned above.
[0072] In one aspect, the present invention provides an ophthalmic product comprising a sealed, autoclave-sterilized package comprising a post-autoclaving packaging solution and a ready-to-use silicone hydrogel contact lens immersed therein, wherein the post-autoclaving packaging solution is a buffered saline solution having a pH of about 6.0 to about 8.0 (preferably about 6.5 to about 7.5) and comprises a polymeric surfactant, the polymeric surfactant comprising at least one hydrophilic poly(oxyethylene) segment and at least one hydrophobic poly(oxybutylene) segment, and having an HLB value of about 11 to about 16 and a number average molecular weight of about 800 to about 20,000 Daltons (preferably about 800 to about 10,000 Daltons, more preferably about 1,000 to about 8,000 Daltons); The ready-to-use silicone hydrogel contact lenses are obtained by placing a preformed silicone hydrogel contact lens in a pre-autoclaved packaging solution containing a polymeric surfactant within the package, sealing and autoclaving, the ready-to-use silicone hydrogel contact lenses having no coating thereon, and the ready-to-use silicone hydrogel contact lenses have a denaturing effect of at least 0.2 μg / lens / 24 hours (preferably at least 0.4 μg / lens / 24 hours, more preferably at least 0.6 μg / lens / 24 hours, even more preferably at least 0.8 μg / lens / 24 hours, and most preferably at least 1.0 μg / lens / 24 hours) as measured in an aqueous extraction process consisting of seven cycles of simulated daily wear extraction.The ready-to-use silicone hydrogel contact lens comprises a polymeric surfactant physically distributed within the polymer matrix of the ready-to-use silicone hydrogel contact lens as evidenced by having an ability to release the polymeric surfactant in an amount of 0.0 μg / lens / 24 hours, the ability to release the polymeric surfactant being the amount of polymeric surfactant released per lens over 24 hours into the extraction medium used in the last cycle of seven cycles of simulated one-day-wear extraction, the ready-to-use silicone hydrogel contact lens having a first static water contact angle, WCA, of about 75° or less (preferably about 70° or less, more preferably about 65° or less, and even more preferably about 60° or less) measured by the Sessile Drop Method directly from the sealed package. OOP and a second static water contact angle of about 85° or less (preferably about 80° or less, more preferably 75° or less, and even more preferably 70° or less) measured by the sessile drop method immediately after seven cycles of simulated one-day wear extraction, WCA 7_S1DW and further has an oxygen permeability of at least 50 barrer, an elastic modulus of about 0.2 MPa to about 1.5 MPa, and an equilibrium moisture content of about 38% to about 80% by weight.
[0073] In another aspect, the present invention provides a method for producing an ophthalmic product, the method comprising the steps of: a) sealing a preformed silicone hydrogel contact lens in a container containing a pre-autoclaved packaging solution, the preformed silicone hydrogel contact lens having no coating and having an oxygen permeability of at least 50 barrer, an elastic modulus of about 0.2 MPa to about 1.5 MPa, and an equilibrium water content of about 38% to about 80% by weight, and the pre-autoclaved packaging solution being a buffered solution having a pH of about 6.0 to about 8.0 (preferably about 6.5 to about 7.5). a) dissolving the preformed silicone hydrogel contact lens in a sealed package for at least about 30 minutes; and b) dissolving the preformed silicone hydrogel contact lens in a sealed package for at least about 30 minutes; and autoclaving the lens for 10 minutes to obtain an ophthalmic product, the ophthalmic product comprising a ready-to-use silicone hydrogel contact lens in a sealed and autoclaved package, the ready-to-use silicone hydrogel contact lens comprising a polymeric surfactant physically distributed within a polymer matrix of the ready-to-use silicone hydrogel contact lens as evidenced by the ability to release the polymeric surfactant in an amount of at least 0.2 μg / lens / 24 hours (preferably at least 0.4 μg / lens / 24 hours, more preferably at least 0.6 μg / lens / 24 hours, even more preferably at least 0.8 μg / lens / 24 hours, and most preferably at least 1.0 μg / lens / 24 hours) as measured in an aqueous extraction process consisting of seven cycles of simulated daily wear extraction, and a first static water contact angle (WCA) of about 75° or less (preferably about 70° or less, more preferably about 65° or less, and even more preferably about 60° or less) as measured by the Sessile Drop Method directly from the sealed package. OOPand a second static water contact angle of about 85° or less (preferably about 80° or less, more preferably 75° or less, and even more preferably 70° or less) measured by the sessile drop method immediately after seven cycles of simulated one-day wear extraction, WCA 7_S1DW and wherein the polymeric surfactant release capacity is the amount of polymeric surfactant released per lens over 24 hours into the extraction medium used in the last cycle of 7 cycles of simulated daily wear extraction.
[0074] According to the present invention, the first static water contact angle, WCA, of the ready-to-use SiHy contact lens is OOP originates from the polymeric surfactant adsorbed on the surface of the ready-to-use SiHy contact lens and in the area just below the lens surface during autoclaving, while the second static water contact angle, WCA 7_S1DW originates from polymeric surfactants that were physically absorbed and distributed in the polymer matrix of the ready-to-use SiHy during autoclaving and migrated from the deep inner regions of the lens to the surface regions just below and onto the lens surface during the last of seven simulated daily wear-extraction cycles.
[0075] Lens packages (or containers) are well known to those skilled in the art for autoclaving and storing contact lenses. Any lens package can be used in the present invention. Preferably, the lens package is a blister package comprising a base and a cover, the cover being removably sealed to the base, and the base comprising a cavity for receiving a sterile packaging solution and a contact lens.
[0076] The lenses are packaged in individual packages, sealed, and autoclaved (e.g., sterilized under pressure in an autoclave at about 120° C. or higher for about 30 to about 45 minutes) before being distributed to users. Those skilled in the art will be familiar with methods of sealing and autoclaving lens packages.
[0077] In accordance with the present invention, the pre-autoclaving or post-autoclaving packaging solution is any aqueous solution used for storing contact lenses that is ophthalmically compatible and known to those skilled in the art.
[0078] The pre-autoclaving or post-autoclaving packaging solution of the present invention is a buffered saline solution.
[0079] As used herein, the term "buffered saline" refers to an aqueous solution containing about 0.15% to 0.95% by weight of one or more salts (e.g., sodium chloride, potassium chloride, or other ophthalmically compatible salts known to those of skill in the art) and one or more buffering agents to maintain a saline pH.
[0080] The packaging solution before or after autoclaving contains one or more buffers to maintain the pH of the packaging solution in a physiologically acceptable range of about 6 to about 8 (preferably about 6.5 to about 7.5). Any known physiologically compatible buffer may be used. Suitable buffers as components of the contact lens care composition according to the invention are known to those skilled in the art. Examples are boric acid, borates such as sodium borate, citric acid, citrates such as potassium citrate, bicarbonates such as sodium bicarbonate, TRIS (2-amino-2-hydroxymethyl-1,3-propanediol), Bis-Tris (Bis-(2-hydroxyethyl)-imino-tris-(hydroxymethyl)-methane), bis-aminopolyols, triethanolamine, ACES (N-(2-hydroxyethyl)-2-aminoethanesulfonic acid), BES (N ,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid), HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid), MES (2-(N-morpholino)ethanesulfonic acid), MOPS (3-[N-morpholino]-propanesulfonic acid), PIPES (piperazine-N,N'-bis(2-ethanesulfonic acid), TES (N-[tris(hydroxymethyl)methyl]-2-aminoethanesulfonic acid), their salts, phosphate buffer (e.g. Na 2 HPO 4 , NaH 2 PO 4 and K.H. 2 PO 4 ), or mixtures thereof. Preferred buffers are borate buffer and phosphate buffer. The amount of each buffer is that amount necessary to be effective in achieving a pH of the composition of about 6.5 to about 7.5. Typically, it is present in an amount of 0.001% to 2% by weight, preferably 0.01% to 1% by weight, and most preferably about 0.05% to about 0.30% by weight.
[0081] According to the present invention, the pre-autoclaving and post-autoclaving packaging solutions contain a polymeric surfactant, which must contain at least one poly(oxyethylene) segment as the hydrophilic component and a poly(oxybutylene) segment as the hydrophobic component. This may be a diblock copolymer, designated as PEO-PBO, a triblock copolymer, designated as PEO-PBO-PEO or PBO-PEO-PBO, or other block type configurations. Unless expressly indicated to the contrary, all references herein to "PEO-PBO block copolymers" include all of the aforementioned forms. These copolymers may also be described in terms of approximate or average values assigned to each repeating group. For example, R-(EO) 20 (BO) 5 -H, the average number of oxyethylene (EO) groups is 20, and the average number of oxybutylene (BO) groups is 5.
[0082] The preferred polymeric surfactants of the present invention are diblock copolymers of the following general formula: R-(EO) m (BO) n -H(S1) wherein R is selected from the group consisting of hydrogen, methyl, ethyl, propyl, and butyl; m is an integer having an average value from 10 to 250, and n is an integer having an average value from 5 to 125, provided that the value of m / n is from about 2:1 to about 10:1, preferably from about 3:1 to about 6:1.
[0083] Particularly preferred are PEO-PBO diblock copolymers of the following general formula: [ka] wherein R is selected from the group consisting of hydrogen, methyl, ethyl, propyl, and butyl; m is an integer having an average value from 10 to 250, and n is an integer having an average value from 5 to 125, provided that the value of m / n is from about 2:1 to about 10:1, preferably from about 3:1 to about 6:1.
[0084] Most preferred are copolymers of formula (S2) where R is methyl, m has an average value of 45, and n has an average value of 10.
[0085] The PEO-PBO block copolymers utilized in the present invention have a molecular weight in the range of 800 to about 10,000 daltons, more preferably in the range of 1,000 to about 8,000 daltons.
[0086] According to the present invention, the number average molecular weight of the polymer surfactant is 1 Determined according to H NMR spectroscopy. In determining the molecular weight of polymers 1 The use of H NMR spectroscopy is e.g. JUIzunobi & C. L. Higginbotham, J. Chem. S.Maiti,Eur.Polym.J.1986,22:1001-1008;KJLiu,Makromol.Chem.1968,116:146-151;FWYeager&J.W.Becker,Anal.Chem.1977,49:722 -724;EGBrame,RCFerguson,GJThomas,Anal.Chem.1967,39:517-521;TFPage&W.E.Bresler,Anal.Chem.1964,36:1981-1985;T.Cosgrove et al.,Langmuir 2015,31:8469-8477; GB Shah, exPRESS Polm. Lett. 2008,2:829-834; KJ Liu, Macromecules, 1968,1:213-217; K. Paulsen & D. Frasco, ThermoFisher Application Note Pub. No. AN52907_E_11 / 16M(2016) and other publications.
[0087] The PEO-PBO block copolymers described above can be synthesized according to the procedures described in US Pat. No. 8,318,144, which is incorporated herein by reference in its entirety.
[0088] It has been found that if the concentration of polymeric surfactant in the packaging solution before autoclaving is too high, the ready-to-use SiHy contact lenses may have a significant change in lens diameter due to the penetration of a significant amount of the polymeric surfactant into the lens. According to the present invention, the amount of polymeric surfactant in the packaging solution before autoclaving is selected to ensure that the difference in lens diameter between the ready-to-use SiHy contact lenses autoclaved in a packaging solution containing a polymeric surfactant according to the present invention and a control lens, which is a preformed SiHy contact lens autoclaved in phosphate buffered saline without the polymeric surfactant, is less than about 0.20 mm (preferably about 0.17 mm, more preferably about 0.14 mm, even more preferably about 0.11 mm), and to ensure that the ready-to-use SiHy contact lenses contain at least about 25 μg / lens (preferably at least about 30 μg / lens, more preferably at least about 35 μg / lens, even more preferably at least about 40 μg / lens, and most preferably at least about 50 or 60 or 70 or 80 or 90 μg / lens).
[0089] In a preferred embodiment, the amount of polymeric surfactant in the packaging solution before autoclaving is about 0.005% by weight to about 0.038% by weight (preferably about 0.007% by weight to about 0.036% by weight, more preferably about 0.008% by weight to 0.034% by weight, even more preferably about 0.009% by weight to 0.032% by weight, and most preferably about 0.010% by weight to 0.030% by weight).
[0090] According to the present invention, the amount of polymeric surfactant in a ready-to-use SiHy contact lens is an average value obtained by averaging the amounts of polymeric surfactant in five ready-to-use SiHy contact lenses. The amount of polymeric surfactant in each ready-to-use SiHy contact lens is determined by first completely extracting the polymeric surfactant from the ready-to-use SiHy contact lens with an extraction medium (e.g., a 1:1 mixture of acetone / hexane) and then measuring the amount of polymeric surfactant in the extraction medium.
[0091] It is also understood that the duration of autoclaving can also affect the amount of polymeric surfactant incorporated by the ready-to-use SiHy contact lenses: the longer the autoclaving time, the greater the amount of polymeric surfactant incorporated by the ready-to-use SiHy contact lenses.
[0092] The pre-autoclaved packaging solutions according to the invention are preferably formulated so that they are isotonic with tear fluid. A solution isotonic with tear fluid is usually understood to be a solution whose concentration corresponds to that of a 0.9% sodium chloride solution (308 mOsm / kg). Deviations from this concentration are possible throughout.
[0093] Isotonicity with tears, or another desired tonicity, can be adjusted by adding organic or inorganic substances that affect tonicity. Suitable ophthalmologically acceptable tonicity agents include, but are not limited to, sodium chloride, potassium chloride, glycerol, propylene glycol, polyols, mannitol, sorbitol, xylitol, and mixtures thereof. Preferably, the majority of the tonicity of the solution is provided by one or more compounds selected from the group consisting of non-halide-containing electrolytes (e.g., sodium bicarbonate) and non-electrolyte compounds. The tonicity of the solution is typically adjusted to a range of about 200 to about 450 milliosmoles (mOsm), preferably about 250 to 350 mOsm.
[0094] In a preferred embodiment, the pre-autoclaved packaging solution comprises from about 0.1% to about 2% by weight of a high molecular weight hydrophilic polymer (i.e., having a number average molecular weight of at least 100,000 Daltons, preferably at least 200,000 Daltons). Preferably, the high molecular weight hydrophilic polymer is polyvinylpyrrolidone, or more preferably, a copolymer of N-vinylpyrrolidone and at least one amino-containing vinyl monomer selected from the group consisting of alkylaminoalkyl methacrylates having 8 to 15 carbons, alkylaminoalkyl acrylates having 7 to 15 carbon atoms, dialkylaminoalkyl methacrylates having 8 to 20 carbon atoms, dialkylamino-alkyl acrylates having 7 to 20 carbon atoms, and N-vinyl alkyl amides having 3 to 10 carbon atoms.
[0095] According to the present invention, the number average molecular weight of the high molecular weight hydrophilic polymer is determined by GPC / RI (refractive index) / LS (light scattering) method under the following conditions:
[0096] [Table 1]
[0097] Examples of amino-containing vinyl monomers include, but are not limited to, alkylaminoalkyl methacrylates having 8 to 15 carbon atoms, alkylaminoalkyl methacrylates having 7 to 15 carbon atoms, dialkylaminoalkyl methacrylates having 8 to 20 carbon atoms, dialkylaminoalkyl acrylates having 7 to 20 carbon atoms, and N-vinyl alkylamides having 3 to 10 carbon atoms. Examples of preferred N-vinyl alkylamides include, but are not limited to, N-vinyl formamide, N-vinyl acetamide, N-vinyl isopropylamide, and N-vinyl-N-methyl acetamide.
[0098] Examples of preferred copolymers include, but are not limited to, copolymers of N-vinylpyrrolidone and dimethylaminoethyl methacrylate. Such preferred copolymers are commercially available, for example Copolymer 845 and Copolymer 937 from ISP.
[0099] It is believed that in pre-autoclaving packaging solutions for packaging and autoclaving uncoated preformed SiHy contact lenses, high molecular weight hydrophilic polymers can have a synergistic effect with the polymeric surfactants in reducing the static water contact angle of the ready-to-use SiHy contact lenses (i.e., improve the wettability of the ready-to-use SiHy contact lenses). It is also believed that high molecular weight hydrophilic polymers, particularly polyvinylpyrrolidone, or more preferably copolymers of N-vinylpyrrolidone and at least one amino-containing vinyl monomer, can form complexes with the polymeric surfactants on or near the surface of the silicone hydrogel contact lenses to function as a carrier for the polymeric surfactants, thereby facilitating the uptake of the polymeric surfactants by the polymer matrix of the silicone hydrogel contact lenses.
[0100] The pre-autoclaved packaging solution of the present invention can optionally include a thickening polymer, which may be a water-soluble cellulose-derived polymer, a water-soluble polyvinyl alcohol (PVA), or a combination thereof. Examples of useful cellulose-derived polymers include, but are not limited to, cellulose ethers. Exemplary preferred cellulose ethers are methyl cellulose (MC), ethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose (HEC), hydroxypropyl cellulose (HPC), hydroxypropyl methyl cellulose (HPMC), or mixtures thereof. More preferably, the cellulose ether is hydroxyethyl cellulose (HEC), hydroxypropyl methyl cellulose (HPMC), and mixtures thereof. The cellulose ether is preferably present in the composition in an amount of about 0.1% to about 1% by weight, based on the total weight of the packaging solution.
[0101] According to the present invention, the pre-autoclaved packaging solution may further comprise a mucin-like material, an ophthalmically beneficial material, and / or an additional surfactant.
[0102] Exemplary mucin-like materials include, but are not limited to, polyglycolic acid and polylactide.
[0103] Exemplary ocular beneficial materials include, but are not limited to, 2-pyrrolidone-5-carboxylic acid (PCA), amino acids (e.g., taurine, glycine, etc.), alpha hydroxyl acids (e.g., glycolic acid, lactic acid, malic acid, tartaric acid, mandelic acid, and citric acid and their salts, etc.), linoleic acid and gamma linoleic acid, and vitamins (e.g., B5, A, B6, etc.).
[0104] Examples of preferred surfactants as additional surfactants include, but are not limited to, poloxamers (e.g., Pluronic® F108, F88, F68, F68LF, F127, F87, F77, P85, P75, P104, and P84), polamines (e.g., Tetronic® 707, 1107, and 1307, polyethylene glycol esters of fatty acids (e.g., Tween® 20, Tween® 80), C 12 ~C 18 Included are polyoxyethylene or polyoxypropylene ethers of alkanes (e.g. Brij® 35), polyoxyethylene stearates (Myrj® 52), polyoxyethylene propylene glycol stearate (Atlas® G2612), and amphoteric surfactants under the trade names Mirataine® and Miranol®.
[0105] According to all the various aspects of the present invention, the preformed SiHy contact lens of the present invention can be any SiHy contact lens that is manufactured according to any lens manufacturing process and then does not undergo surface treatment to form a coating thereon.Those skilled in the art are very familiar with how to make SiHy contact lenses.For example, SiHy contact lenses can be manufactured in a conventional "spin casting mold" as described in, for example, U.S. Pat. No. 3,408,429, or by a complete cast molding process in a static form as described in U.S. Pat. Nos. 4,347,198; 5,508,317; 5,583,163; 5,789,464; and 5,849,810, or by lathe cutting of a button of polymer-based material as used to make customized contact lenses.In cast molding, a polymerizable composition (i.e., SiHy lens formulation) is typically dispensed into a mold and cured (i.e., polymerized and / or crosslinked) in the mold to produce a SiHy contact lens.
[0106] Lens molds for making contact lenses, such as SiHy contact lenses, are well known to those skilled in the art and are used, for example, for casting or spin casting. For example, a mold (for casting) typically includes at least two mold pieces (or parts) or mold halves, namely a first and a second mold half. The first mold half defines a first molding (or optical) surface, and the second mold half defines a second molding (or optical) surface. The first and second mold halves are configured to receive each other such that a lens-forming cavity is formed between the first and second molding surfaces. The molding surface of the mold half is the cavity-forming surface of the mold and is in direct contact with the polymerizable composition.
[0107] The method of manufacturing mold pieces for mold casting contact lenses is generally known to those skilled in the art. The method of the present invention is not limited to a specific method of forming a mold. In fact, any method of forming a mold can be used in the present invention. The first and second mold halves can be formed by various techniques, such as injection molding or lathing. Examples of suitable processes for forming mold halves are described in U.S. Patent Nos. 4,444,711; 4,460,534; 5,843,346; and 5,894,002.
[0108] To make the mold for making contact lenses, virtually all materials known in the art for making molds can be used.For example, polymer-based materials such as polyethylene, polypropylene, polystyrene, PMMA, Topas® COC grade 8007-S10 (transparent amorphous copolymer of ethylene and norbornene, Ticona GmbH, Frankfurt, Germany and Summit, New Jersey) can be used.Other materials that allow UV light to pass through can also be used, such as quartz glass and sapphire.
[0109] In a preferred embodiment, a reusable mold is used and the lens-forming composition is chemically cured under the spatial confinement of actinic radiation to form a contact lens. Examples of preferred reusable molds are those disclosed in U.S. Patent Nos. 6,627,124, 6,800,225, 7,384,590 and 7,387,759. Reusable molds can be made of quartz, glass, sapphire, CaF 2 , cyclic olefin copolymers (e.g., Topas® COC grade 8007-S10 (a transparent amorphous copolymer of ethylene and norbornene) from Ticona GmbH, Frankfurt, Germany and Summit, New Jersey, Zeonex® and Zeonor® from Zeon Chemicals LP, Louisville, KY), polymethyl methacrylate (PMMA), polyoxymethylene from DuPont (Delrin), Ultem® (polyetherimide) from GEPlastics, PrimoSpire®, and the like.
[0110] According to the present invention, the polymerizable composition can be introduced (dispensed) into the cavity formed by the mold according to any known method.
[0111] After the polymerizable composition is dispensed into the mold, it is polymerized to produce a SiHy contact lens. Crosslinking can be initiated thermally or chemically, preferably by exposing the polymerizable composition in the mold to spatially confined actinic radiation to crosslink the polymerizable components in the polymerizable composition.
[0112] Opening the mold so that the molded SiHy contact lens can be removed from the mold can be done in a manner known per se.
[0113] The molded SiHy contact lenses are subjected to lens extraction to remove unpolymerized polymerizable components, followed by hydration of the lenses. The extraction solvent can be any solvent known to those skilled in the art. Examples of suitable extraction solvents are described below.
[0114] The preformed SiHy contact lens can be any commercially available SiHy contact lens or can be manufactured according to any known method. For example, in the manufacture of preformed SiHy contact lenses, the SiHy lens formulation for making the SiHy rod used for casting or spin casting or lathe cutting of contact lenses usually includes at least one component selected from the group consisting of silicone-containing vinyl monomers, polysiloxane vinyl crosslinkers, silicone-containing prepolymers, hydrophilic vinyl monomers, hydrophobic vinyl monomers, non-silicone vinyl crosslinkers, free radical initiators (photoinitiators or thermal initiators), silicone-containing prepolymers, and combinations thereof, as known to those skilled in the art. The obtained SiHy contact lens can then be extracted with an extraction solvent to remove unpolymerized components from the obtained lens and subjected to a hydration process, as known to those skilled in the art. In addition, the preformed SiHy contact lens can be a colored contact lens (i.e., a SiHy contact lens with at least one colored pattern printed thereon, as known to those skilled in the art).
[0115] According to the present invention, silicone-containing vinyl monomer can be any silicone-containing vinyl monomer known to those skilled in the art.The preferred silicone-containing vinyl monomer examples include but are not limited to the vinyl monomers having bis(trialkylsilyloxy) alkylsilyl group or tris(trialkylsilyloxy) silyl group, polysiloxane vinyl monomer, 3-methacryloxypropyl pentamethyldisiloxane, t-butyldimethyl-siloxyethyl vinyl carbonate, trimethylsilylethyl vinyl carbonate and trimethylsilylmethyl vinyl carbonate, and their combinations.
[0116] Preferred polysiloxane vinyl monomers, including those of formula (M1), are described later in this application and can be obtained from commercial sources (e.g., Shin-Etsu, Gelest, etc.) and can be prepared, for example, according to the procedures described in U.S. Pat. Nos. 5,070,215, 6,166,236, 6,867,245, 8,415,405, 8,475,529, 8,614,261 and 9,217,813; They can be prepared by reacting ethylene glycol with monoepoxypropyloxypropyl terminated polydimethylsiloxane; by reacting glycidyl (meth)acrylate with monocarbinol terminated polydimethylsiloxane, monoaminopropyl terminated polydimethylsiloxane or monoethylaminopropyl terminated polydimethylsiloxane; or by reacting isocyanatoethyl (meth)acrylate with monocarbinol terminated polydimethylsiloxane according to coupling reactions well known to those skilled in the art.
[0117] Preferred silicone-containing vinyl monomers having bis(trialkylsilyloxy)alkylsilyl or tris(trialkylsilyloxy)silyl groups, respectively, including those of formula (M2), are described later in this application and can be obtained from commercial sources (e.g., Shin-Etsu, Gelest, etc.) and can be prepared according to the procedures described, for example, in U.S. Pat. Nos. 5,070,215, 6,166,236, 7,214,809, 8,475,529, 8,658,748, 9,097,840, 9,103,965, and 9,475,827.
[0118] Any suitable polysiloxane vinyl crosslinker can be used in the present invention. Examples of preferred polysiloxane vinyl crosslinkers include di-(meth)acryloyl-terminated polydimethylsiloxane; divinyl carbonate-terminated polydimethylsiloxane; divinyl carbamate-terminated polydimethylsiloxane; N,N,N',N'-tetrakis(3-methacryloxy-2-hydroxypropyl)-alpha,omega-bis-3-aminopropyl-polydimethylsiloxane; Macromer A, Macromer B, and Macromer C, as described in U.S. Pat. No. 5,760,100. Polysiloxane-containing macromers selected from the group consisting of Macromer C and Macromer D; U.S. Pat. Nos. 4,136,250, 4,153,641, 4,182,822, 4,189,546, 4,343,927, 4,254,248, 4,355,147, 4,276,402, 4,327,203, 4,341,889, 4,486,577, and 4,543,398; Specification, Specification No. 4605712, Specification No. 4661575, Specification No. 4684538, Specification No. 4703097, Specification No. 4833218, Specification No. 4837289, Specification No. 4954586, Specification No. 4 Specification No. 954587, Specification No. 5010141, Specification No. 5034461, Specification No. 5070170, Specification No. 5079319, Specification No. 5039761, Specification No. 5346946, Specification No. 5358995. the polysiloxane-containing macromers disclosed in U.S. Pat. Nos. 5,387,632, 5,416,132, 5,451,617, 5,486,579, 5,962,548, 5,981,675, 6,039,913, and 6,762,264; the polysiloxane-containing macromers disclosed in U.S. Pat. Nos. 4,259,467, 4,260,725, and 4,261,875.
[0119] One class of preferred polysiloxane vinyl crosslinkers is composed of dimethylsiloxane units and one monovalent C siloxane having one methyl substituent and two to six hydroxyl groups. 4 ~C40 and hydrophilized siloxane units each having an organic radical substituent, more preferably a di-(meth)acryloyloxy-terminated polysiloxane vinyl crosslinker of formula (I), which are described later in this application and can be prepared according to the procedures disclosed in U.S. Pat. No. 1,008,1697.
[0120] Another class of preferred polysiloxane vinyl crosslinkers is the vinyl crosslinker of formula (1), which is described later in this application and is available from commercial sources; and can be prepared by reacting glycidyl (meth)acrylate (meth)acryloyl chloride with diamino-terminated polydimethylsiloxane or dihydroxyl-terminated polydimethylsiloxane; can be prepared by reacting isocyanatoethyl (meth)acrylate with dihydroxyl-terminated polydimethylsiloxane, can be prepared by reacting an amino-containing acrylic monomer with a dicarboxyl-terminated polydimethylsiloxane in the presence of a coupling agent (carbodiimide); can be prepared by reacting a carboxyl-containing acrylic monomer with a diamino-terminated polydimethylsiloxane in the presence of a coupling agent (carbodiimide); or can be prepared by reacting a hydroxyl-containing acrylic monomer with a dihydroxyl-terminated polydisiloxane in the presence of a diisocyanate or diepoxy coupling agent.
[0121] Another class of preferred polysiloxane vinyl crosslinkers is the chain extended polysiloxane vinyl crosslinker of any one of formulas (2)-(7), which are described later in this application and can be prepared according to the procedures described in U.S. Pat. Nos. 5,034,461, 5,416,132, 5,449,729, 5,760,100, 7,423,074, 8,529,057, 8,835,525, 8,993,651, and 10,301,451 and U.S. Patent Publication No. 20180100038 A1.
[0122] Any hydrophilic vinyl monomer can be used in the present invention. Examples of preferred hydrophilic vinyl monomers are alkyl(meth)acrylamides (described later in this application), hydroxyl-containing acrylic monomers (described later in this application), amino-containing acrylic monomers (described later in this application), carboxyl-containing acrylic monomers (described later in this application), N-vinylamide monomers (described later in this application), methylene-containing pyrrolidone monomers (i.e., pyrrolidone derivatives having a methylene group attached to the pyrrolidone ring at the 3- or 5-position, respectively) (described later in this application), C 1 ~C 4 acrylic monomers having alkoxyethoxy groups (described later in this application), vinyl ether monomers (described later in this application), allyl ether monomers (described later in this application), phosphorylcholine-containing vinyl-based monomers (described later in this application), N-2-hydroxyethyl vinyl carbamate, N-carboxyvinyl-β-alanine (VINAL), N-carboxyvinyl-α-alanine, and combinations thereof.
[0123] According to the present invention, any hydrophobic vinyl monomer can be included in the present invention.Preferred examples of hydrophobic vinyl monomer include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl valerate, styrene, chloroprene, vinyl chloride, vinylidene chloride, (meth)acrylonitrile, 1-butene, butadiene, vinyl toluene, vinyl ethyl ether, perfluorohexylethyl-thio-carbonyl-aminoethyl-methacrylate, isobornyl (meth)acrylate, trifluoroethyl (meth)acrylate, hexafluoroisopropyl (meth)acrylate, hexafluorobutyl (meth)acrylate and combinations thereof.
[0124] According to the present invention, any non-silicone vinyl crosslinker can be included in the present invention. Examples of preferred non-silicone vinyl crosslinkers are described later in this application.
[0125] Any thermal polymerization initiator can be used in the present invention. Suitable thermal polymerization initiators are known to those skilled in the art and include, for example, peroxides, hydroperoxides, azo-bis(alkyl- or cycloalkylnitriles), persulfates, percarbonates, or mixtures thereof.Examples of suitable thermal polymerization initiators include, but are not limited to, benzoyl peroxide, t-butyl peroxide, t-amyl peroxybenzoate, 2,2-bis(tert-butylperoxy)butane, 1,1-bis(tert-butylperoxy)cyclohexane, 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane, 2,5-bis(tert-butylperoxy)-2,5-dimethyl-3-hexyne, bis(1-(tert-butylperoxy)-1-methylethyl)-1,2-bis(tert-butylperoxy ... tert-butyl)benzene, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, di-t-butyl-dipyroxyphthalate, t-butyl hydroperoxide, t-butyl peracetate, t-butyl peroxybenzoate, t-butyl peroxyisopropyl carbonate, acetyl peroxide, lauroyl peroxide, decanoyl peroxide, dicetyl peroxydicarbonate, di(4-t-butylcyclohexyl) peroxydicarbonate (Perkadox 16S), di(2-ethylhexyl) peroxydicarbonate, t-butyl peroxypivalate (Lupersol 11); t-butyl peroxy-2-ethylhexanoate (Trigonox 21-C50), 2,4-pentanedione peroxide, dicumyl peroxide, peracetic acid, potassium persulfate, sodium persulfate, ammonium persulfate, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (VAZO33), 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride (VAZO44), 2,2'-azobis(2-amidinopropane) dihydrochloride (VAZO50), 2,2'-azobis(2,4-dimethyl 2,2'-azobis(valeronitrile) (VAZO52), 2,2'-azobis(isobutyronitrile) (VAZO64 or AIBN), 2,2'-azobis-2-methylbutyronitrile (VAZO67), 1,1-azobis(1-cyclohexanecarbonitrile) (VAZO88); 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(methylisobutyrate), 4,4'-azobis(4-cyanovaleric acid), and combinations thereof.Preferably, the thermal initiator is 2,2'-azobis(isobutyronitrile) (AIBN or VAZO64).
[0126] Suitable photoinitiators are benzoin methyl ether, diethoxyacetophenone, benzoylphosphine oxide, 1-hydroxycyclohexylphenyl ketone and Darocur and Irgacur types, preferably Darocur 1173® and Darocur 2959®, germanium-based Norrish Type I photoinitiators (e.g., those described in U.S. Pat. No. 7,605,190). Examples of benzoylphosphine initiators include 2,4,6-trimethylbenzoyldiphenylphosphine oxide; bis-(2,6-dichlorobenzoyl)-4-N-propylphenylphosphine oxide; and bis-(2,6-dichlorobenzoyl)-4-N-butylphenylphosphine oxide. Reactive photoinitiators that can be incorporated into macromers or used as special monomers are also suitable. Examples of reactive photoinitiators are those disclosed in EP 632329.
[0127] The SiHy contact lens formulations may also include other necessary ingredients known to those of skill in the art, such as, for example, UV absorbing vinyl monomers, high energy ultraviolet light ("HEVL") absorbing vinyl monomers, visibility colorants (e.g., reactive dyes, polymeric dyes, pigments, or mixtures thereof known to those of skill in the art), antimicrobial agents (e.g., preferably silver nanoparticles), bioactive agents, leachable polymeric lubricants (e.g., non-polymerizable hydrophilic polymers, etc.), leachable tear stabilizers (e.g., phospholipids, monoglycerides, diglycerides, triglycerides, glycolipids, glyceroglycolipids, sphingolipids, sphingoglycolipids, etc.), and mixtures thereof.
[0128] The polymerizable composition (SiHy lens formulation), as known to those skilled in the art, may be a solvent-free clear liquid prepared by mixing all of the polymerizable components with other necessary ingredients, or it may be a solution prepared by dissolving all of the desired components in any suitable solvent, such as a mixture of water and one or more water-miscible solvents, an organic solvent, or a mixture of one or more organic solvents. The term "solvent" refers to a chemical that cannot participate in a free radical polymerization reaction.
[0129] Solventless lens SiHy lens formulations typically include at least one blend vinyl monomer as a reactive solvent to dissolve all other polymerizable components of the solventless SiHy lens formulation. Examples of preferred blend vinyl monomers are described later in this application. Preferably, methyl methacrylate is used as the blend vinyl monomer in the preparation of the solventless SiHy lens formulation.
[0130] In the present invention, any solvent can be used. Examples of preferred organic solvents include, but are not limited to, tetrahydrofuran, tripropylene glycol methyl ether, dipropylene glycol methyl ether, ethylene glycol n-butyl ether, ketones (e.g., acetone, methyl ethyl ketone, etc.), diethylene glycol n-butyl ether, diethylene glycol methyl ether, ethylene glycol phenyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, dipropylene glycol methyl ether acetate, propylene glycol n-propyl ether, dipropylene glycol n-propyl ether, tripropylene glycol n-butyl ether, propylene glycol n-butyl ether, dipropylene glycol n-butyl ether, tripropylene glycol n-butyl ether, ... glycol phenyl ether, dipropylene glycol dimethyl ether, polyethylene glycol, polypropylene glycol, ethyl acetate, butyl acetate, amyl acetate, methyl lactate, ethyl lactate, i-propyl lactate, methylene chloride, 2-butanol, 1-propanol, 2-propanol, menthol, cyclohexanol, cyclopentanol and exonorborneol, 2-pentanol, 3-pentanol, 2-hexanol, 3-hexanol, 3-methyl-2-butanol, 2-heptanol, 2-octanol, 2-nonanol, 2-decanol, 3-octanol, norborneol, tert-butanol, tert-amyl alcohol, 2-methyl-2-pentanol, 2,3-dimethyl-2-butanol, 3-methyl-3-pentanol, 1-methylcyclohexanol, 2-methyl-2-hexanol, 3,7-Dimethyl-3-octanol, 1-chloro-2-methyl-2-propanol, 2-methyl-2-heptanol, 2-methyl-2-octanol, 2-2-methyl-2-nonanol, 2-methyl-2-decanol, 3-methyl-3-hexanol, 3-methyl-3-heptanol, 4-methyl-4-heptanol, 3-methyl-3-octanol, 4-methyl-4-octanol, 3-methyl-3-nonanol, 4-methyl-4-nonanol, 3-methyl-3-octanol, 3-ethyl-3-hexanol, 3-methyl-3-heptanol, 4-ethyl-4-heptanol, 4-propyl-4-heptanol, 4-isopropyl-4-heptanol, 2,4-dimethyl-2-pentanol, 1-methylcyclopentanol, Examples of suitable cyclopentanols include 1-ethylcyclopentanol, 1-ethylcyclopentanol, 3-hydroxy-3-methyl-1-butene, 4-hydroxy-4-methyl-1-cyclopentanol, 2-phenyl-2-propanol, 2-methoxy-2-methyl-2-propanol, 2,3,4-trimethyl-3-pentanol, 3,7-dimethyl-3-octanol, 2-phenyl-2-butanol, 2-methyl-1-phenyl-2-propanol and 3-ethyl-3-pentanol, 1-ethoxy-2-propanol, 1-methyl-2-pyrrolidone, N,N-dimethylpropionamide, dimethylformamide, dimethylacetamide, dimethylpropionamide, N-methylpyrrolidone, and mixtures thereof.
[0131] Numerous SiHy lens formulations have been described in numerous patents and patent applications published up to the filing date of this application and have been used in the manufacture of commercially available SiHy contact lenses. Examples of commercially available SiHy contact lenses include, but are not limited to, asmofilcon A, balafilcon A, confilcon A, delefilcon A, eflofilcon A, enfilcon A, funfilcon A, galyfilcon A, lotrafilcon A, lotrafilcon B, narafilcon A, narafilcon B, senofilcon A, senofilcon B, senofilcon C, sumafilcon A, somofilcon A, and stenfilcon A.
[0132] The SiHy lens formulation (ie, the polymerizable composition) can be thermally or chemically cured (polymerized), preferably in a mold for casting the contact lens, as known to those skilled in the art.
[0133] The thermal polymerization is conveniently carried out at a temperature of, for example, 25 to 120° C., preferably 40 to 100° C. The reaction time may vary within a wide range, but is conveniently, for example, 1 to 24 hours, or preferably 2 to 12 hours. It is advantageous to previously degas the components and solvents used in the polymerization reaction and to carry out the copolymerization reaction under an inert atmosphere, for example under an atmosphere of nitrogen or argon.
[0134] Actinic polymerization can then be induced by actinic radiation, such as light, especially UV or visible light of suitable wavelengths. If necessary, suitable photosensitizers can be added to provide appropriate control of the spectral requirements.
[0135] Although various embodiments of the present invention have been described using specific terms, devices, and methods, such descriptions are for illustrative purposes only. The terms used are terms of description rather than of limitation. As will be apparent to those skilled in the art, many variations and modifications of the present invention may be made by those skilled in the art without departing from the spirit and scope of the novel concepts of the present disclosure. In addition, it should be understood that aspects of the various embodiments of the present invention may be interchanged in whole or in part, or may be combined in any manner and / or used together, as set forth below:
[0136] 1. An ophthalmic product comprising a sealed, autoclaved package containing a post-autoclaved packaging solution and a ready-to-use silicone hydrogel contact lens immersed therein, The autoclaved packaging solution is a buffered saline solution having a pH of about 6.0 to about 8.0 and includes a polymeric surfactant, the polymeric surfactant including at least one hydrophilic poly(oxyethylene) segment and at least one hydrophobic poly(oxybutylene) segment and having an HLB value of about 11 to about 16 and a number average molecular weight of about 800 to about 20,000 Daltons, and the ready-to-use silicone hydrogel contact lens is obtained by placing a preformed silicone hydrogel contact lens in a package, sealing and autoclaving, in a pre-autoclaved packaging solution including the polymeric surfactant, the ready-to-use silicone hydrogel contact lens does not have a coating thereon, and ... The ready-to-use silicone hydrogel contact lens comprises a polymeric surfactant physically distributed within a polymer matrix of the ready-to-use silicone hydrogel contact lens as evidenced by an ability to release the polymeric surfactant in an amount of at least 0.2 μg / lens / 24 hours as measured in an aqueous extraction process consisting of seven cycles of simulated one-day-wear extraction, the ability to release the polymeric surfactant being the amount of the polymeric surfactant released per lens over 24 hours into an extraction medium used in the last cycle of seven cycles of simulated one-day-wear extraction, the ready-to-use silicone hydrogel contact lens having a first static water contact angle of less than or equal to about 75° as measured by a sessile drop method directly removed from the sealed package, a WCA OOP and a second static water contact angle of about 85° or less measured by the sessile drop method immediately after seven cycles of the simulated one-day wear extraction, WCA 7_S1DW and an oxygen permeability of at least 50 barrer, an elastic modulus of about 0.2 MPa to about 1.5 MPa, and an equilibrium water content of about 38% to about 80% by weight. 2. a) sealing a preformed silicone hydrogel contact lens in a container containing a pre-autoclaved packaging solution, the preformed silicone hydrogel contact lens being free of a coating and having an oxygen permeability of at least 50 barrer, a modulus of elasticity of about 0.2 MPa to about 1.5 MPa, and an equilibrium water content of about 38% to about 80% by weight, the pre-autoclaved packaging solution being a buffered saline solution having a pH of about 6.0 to about 8.0, and comprising a polymeric surfactant, the polymeric surfactant comprising at least one hydrophilic poly(oxyethylene) segment and at least one hydrophobic poly(oxybutylene) segment, having an HLB value of about 11 to about 16, and a number average molecular weight of about 800 to about 20,000 Daltons; and b) autoclaving the sealed package containing the preformed silicone hydrogel contact lens therein for at least about 30 minutes to obtain an ophthalmic product, the ophthalmic product comprising a ready-to-use silicone hydrogel contact lens immersed in a post-autoclaved packaging solution in the sealed and autoclaved package, the ready-to-use silicone hydrogel contact lens comprising the polymeric surfactant physically distributed within the polymer matrix of the ready-to-use silicone hydrogel contact lens as evidenced by having an ability to release the polymeric surfactant in an amount of at least 0.2 μg / lens / 24 hours as measured in an aqueous extraction process consisting of seven cycles of simulated daily wear extraction, and having a first static water contact angle of about 75° or less as measured by a Sessile Drop Method directly removed from the sealed package, WCA OOP and a second static water contact angle of about 85° or less measured by the sessile drop method immediately after seven cycles of the simulated one-day wear extraction, WCA 7_S1DW and wherein said polymeric surfactant release capacity is the amount of polymeric surfactant released per lens over a 24 hour period into an extraction medium used in the last of 7 cycles of said simulated daily wear extraction; A method for producing an ophthalmic product comprising: 3. The ophthalmic product of embodiment 1 or the method of embodiment 2, wherein the polymeric surfactant has a number average molecular weight of about 800 to about 10,000 Daltons. 4. The ophthalmic product of embodiment 1 or the method of embodiment 2, wherein the polymeric surfactant has a number average molecular weight of about 1,000 to about 8,000 Daltons. 5. The ophthalmic product of embodiment 1, 3, or 4 or the method of any one of embodiments 2-4, wherein the packaging solution after autoclaving has a pH of about 6.5 to about 7.5. 6. The ready-to-use silicone hydrogel contact lens has a WCA of about 70° or less measured by the Sessile Drop Method directly from the sealed package. OOP and optionally having a WCA of about 80° or less measured by a sessile drop method immediately after seven cycles of the simulated one-day wearing extraction. 7_S1DW The ophthalmic product according to any one of embodiments 1 and 3 to 5 or the method according to any one of embodiments 2 to 5, comprising: 7. The ready-to-use silicone hydrogel contact lens has a WCA of about 65° or less measured by the Sessile Drop Method directly from the sealed package. OOP and optionally having a WCA of about 75° or less as measured by a sessile drop method immediately after seven cycles of the simulated one-day wearing extraction. 7_S1DW The ophthalmic product according to any one of embodiments 1 and 3 to 5 or the method according to any one of embodiments 2 to 5, comprising: 8. The ready-to-use silicone hydrogel contact lens has a WCA of about 60° or less measured by the Sessile Drop Method directly from the sealed package. OOP and optionally having a WCA of about 70° or less measured by a sessile drop method immediately after seven cycles of the simulated one-day wearing extraction. 7_S1DW The ophthalmic product according to any one of embodiments 1 and 3 to 5 or the method according to any one of embodiments 2 to 5, comprising: 9. The ophthalmic product of any one of embodiments 1 and 3-8 or the method of any one of embodiments 2-8, wherein the ready-to-use silicone hydrogel contact lens has the capacity to release the polymeric surfactant in an amount of at least 0.4 μg / lens / 24 hours as measured in the aqueous extraction process consisting of 7 cycles of the simulated daily wear extraction. 10. The ophthalmic product of any one of embodiments 1 and 3-8 or the method of any one of embodiments 2-8, wherein the ready-to-use silicone hydrogel contact lens has the ability to release the polymeric surfactant in an amount of at least 0.6 μg / lens / 24 hours as measured in the aqueous extraction process consisting of 7 cycles of the simulated daily wear extraction. 11. The ophthalmic product of any one of embodiments 1 and 3-8 or the method of any one of embodiments 2-8, wherein the ready-to-use silicone hydrogel contact lens has the capacity to release the polymeric surfactant in an amount of at least 0.8 μg / lens / 24 hours as measured in the aqueous extraction process consisting of 7 cycles of the simulated daily wear extraction. 12. The ophthalmic product of any one of embodiments 1 and 3-8 or the method of any one of embodiments 2-8, wherein the ready-to-use silicone hydrogel contact lens has the capacity to release the polymeric surfactant in an amount of at least 1.0 μg / lens / 24 hours as measured in the aqueous extraction process consisting of 7 cycles of the simulated daily wear extraction. 13. The ophthalmic product according to any one of embodiments 1 and 3 to 12 or the method according to any one of embodiments 2 to 12, wherein the polymeric surfactant is a diblock copolymer designated PEO-PBO or a triblock copolymer designated PEO-PBO-PEO or BO-PEO-PBO, where PEO represents a poly(oxyethylene) segment and PBO represents a poly(oxybutylene) segment. 14. The ophthalmic product according to any one of embodiments 1 and 3 to 12 or the method according to any one of embodiments 2 to 12, wherein the polymeric surfactant is a diblock copolymer of formula (S1). RO-(EO) m (BO) n -H(S1) where R is selected from the group consisting of hydrogen, methyl, ethyl, propyl, and butyl; EO is ethylene oxide-C 2 H 4 O-; BO is butylene oxide-C 4 H 8 O-; m is an integer having an average value of 10 to 250; and n is an integer having an average value of 5 to 125, provided that the value of m / n is from about 2:1 to about 10:1. 15. The ophthalmic product or method of embodiment 14, wherein, in formula (S1), the value of m / n is from about 3:1 to about 6:1. 16. The ophthalmic product according to any one of embodiments 1 and 3 to 12 or the method according to any one of embodiments 2 to 12, wherein the polymeric surfactant is a diblock copolymer of formula (S2). [ka] wherein R is selected from the group consisting of hydrogen, methyl, ethyl, propyl, and butyl; m is an integer having an average value from 10 to 250; and n is an integer having an average value from 5 to 125, with the proviso that the value of m / n is from about 2:1 to about 10:1. 17. The ophthalmic product or method of embodiment 16, wherein, in formula (S1), the value of m / n is from about 3:1 to about 6:1. 18. The ophthalmic product or method of embodiment 16 or 17, wherein in formula (S1), R is methyl. 19. The ophthalmic product or method of any one of embodiments 16 to 18, wherein in formula (S1), m has an average value of 45 and n has an average value of 10. 20. The ophthalmic product of any one of embodiments 1 and 3-19 or the method of any one of embodiments 2-19, wherein the ready-to-use silicone hydrogel contact lens comprises at least about 25 μg of the polymeric surfactant per lens. 21. The ophthalmic product of any one of embodiments 1 and 3-19 or the method of any one of embodiments 2-19, wherein the ready-to-use silicone hydrogel contact lens comprises at least about 30 μg of the polymeric surfactant per lens. 22. The ophthalmic product of any one of embodiments 1 and 3-19 or the method of any one of embodiments 2-19, wherein the ready-to-use silicone hydrogel contact lens comprises at least about 35 μg of the polymeric surfactant per lens. 23. The ophthalmic product of any one of embodiments 1 and 3-19 or the method of any one of embodiments 2-19, wherein the ready-to-use silicone hydrogel contact lens comprises at least about 40 μg of the polymeric surfactant per lens. 24. The ophthalmic product of any one of embodiments 1 and 3-19 or the method of any one of embodiments 2-19, wherein the ready-to-use silicone hydrogel contact lens comprises at least about 50 μg of the polymeric surfactant per lens. 25. The ophthalmic product of any one of embodiments 1 and 3-19 or the method of any one of embodiments 2-19, wherein the ready-to-use silicone hydrogel contact lens comprises at least about 60 μg of the polymeric surfactant per lens. 26. The ophthalmic product of any one of embodiments 1 and 3-19 or the method of any one of embodiments 2-19, wherein the ready-to-use silicone hydrogel contact lens comprises at least about 70 μg of the polymeric surfactant per lens. 27. The ophthalmic product of any one of embodiments 1 and 3-19 or the method of any one of embodiments 2-19, wherein the ready-to-use silicone hydrogel contact lens comprises at least about 80 μg of the polymeric surfactant per lens. 28. The ophthalmic product of any one of embodiments 1 and 3-19 or the method of any one of embodiments 2-19, wherein the ready-to-use silicone hydrogel contact lens comprises at least about 90 μg of the polymeric surfactant per lens. 29. The ophthalmic product of any one of embodiments 1 and 3-28 or the method of any one of embodiments 2-28, wherein the pre-autoclaving packaging solution further comprises about 0.1% to about 2% by weight of a hydrophilic polymer having a number average molecular weight of at least 100,000 Daltons. 30. The ophthalmic product of any one of embodiments 1 and 3-28 or the method of any one of embodiments 2-28, wherein the pre-autoclaved packaging solution further comprises about 0.1% to about 2% by weight of a hydrophilic polymer having a number average molecular weight of at least 200,000 Daltons. 31. The ophthalmic product or method of embodiment 29 or 30, wherein the hydrophilic polymer is polyvinylpyrrolidone. 32. The ophthalmic product or method of embodiment 29 or 30, wherein the hydrophilic polymer is a copolymer of N-vinylpyrrolidone and at least one amino-containing vinyl monomer selected from the group consisting of alkylaminoalkyl methacrylates having 8 to 15 carbon atoms, alkylaminoalkyl acrylates having 7 to 15 carbon atoms, dialkylaminoalkyl methacrylates having 8 to 20 carbon atoms, dialkylaminoalkyl acrylates having 7 to 20 carbon atoms, and N-vinylalkylamides having 3 to 10 carbon atoms. 33. The ophthalmic product or method of embodiment 31 or 32, wherein the amino-containing vinyl monomer is dimethylaminoethyl methacrylate or dimethylaminoethyl acrylate. 34. The ophthalmic product of any one of embodiments 1 and 3 to 33 or the method of any one of embodiments 2 to 33, wherein the ready-to-use silicone hydrogel contact lens has an oxygen permeability of about 60 to about 180 barrer. 35. The ophthalmic product of any one of embodiments 1 and 3 to 33 or the method of any one of embodiments 2 to 33, wherein the ready-to-use silicone hydrogel contact lens has an oxygen permeability of about 70 to about 180 barrer. 36. The ophthalmic product of any one of embodiments 1 and 3 to 33 or the method of any one of embodiments 2 to 33, wherein the ready-to-use silicone hydrogel contact lens has an oxygen permeability of about 80 to about 180 barrer. 37. The ophthalmic product of any one of embodiments 1 and 3 to 33 or the method of any one of embodiments 2 to 33, wherein the ready-to-use silicone hydrogel contact lens has an oxygen permeability of about 90 to about 180 barrer. 38. The ophthalmic product of any one of embodiments 1 and 3-37 or the method of any one of embodiments 2-37, wherein the ready-to-use silicone hydrogel contact lens has an equilibrium water content of about 40% to about 80% by weight. 39. The ophthalmic product of any one of embodiments 1 and 3-37 or the method of any one of embodiments 2-37, wherein the ready-to-use silicone hydrogel contact lens has an equilibrium water content of about 45% to about 80% by weight. 40. The ophthalmic product of any one of embodiments 1 and 3-39 or the method of any one of embodiments 2-39, wherein the ready-to-use silicone hydrogel contact lens has an elastic modulus of 0.3 MPa to about 1.3 MPa. 41. The ophthalmic product of any one of embodiments 1 and 3-39 or the method of any one of embodiments 2-39, wherein the ready-to-use silicone hydrogel contact lens has an elastic modulus of 0.4 MPa to about 1.2 MPa. 42. The ophthalmic product of any one of embodiments 1 and 3-41 or the method of any one of embodiments 2-41, wherein the preformed silicone hydrogel contact lens is an essentially wettable silicone hydrogel contact lens. 43. The ophthalmic product of any one of embodiments 1 and 3-42 or the method of any one of embodiments 2-42, wherein the preformed silicone hydrogel contact lens is composed of a silicone hydrogel material comprising repeat units of at least one silicone-containing vinyl monomer selected from the group consisting of vinyl monomers having bis(trialkylsilyloxy)alkylsilyl groups, vinyl monomers having tris(trialkylsilyloxy)silyl groups, polysiloxane vinyl monomers, 3-methacryloxypropylpentamethyldisiloxane, t-butyldimethyl-siloxyethyl vinyl carbonate, trimethylsilylethyl vinyl carbonate, and trimethylsilylmethyl vinyl carbonate, and combinations thereof. 44. The at least one silicone-containing vinyl monomer is represented by the formula (M1) or (M2): [ka] (wherein a1 is zero or 1; R o is H or methyl; X o is O or NR 1 And;L 1 is C 2 ~C 8 an alkylene divalent radical, or [ka] is a divalent radical of; L 1 ' is a C having 0 or 1 hydroxyl group 2 ~C 8 is an alkylene divalent radical; L 1 " is a C having 0 or 1 hydroxyl group 3 ~C 8 is an alkylene divalent radical; X 1 , O, NR 1 , NHCOO, OCONH, CONR 1 or NR 1 CO;R 1 is H or C having 0 to 2 hydroxyl groups1 ~C 4 R is alkyl; t1 and R t2 are independent of each other, C 1 ~C 6 is alkyl; X 1 ' is O or NR 1 q1 is an integer of 1 to 30; q2 is an integer of 0 to 30; n1 is an integer of 3 to 40; and r1 is an integer of 2 or 3. 44. The ophthalmic product or method of embodiment 43, comprising a vinyl monomer of 45. The at least one silicone-containing vinyl monomer is selected from the group consisting of tris(trimethylsilyloxy)silylpropyl(meth)acrylate, [3-(meth)acryloxy-2-hydroxypropyloxy]propylbis(trimethylsiloxy)methylsilane, [3-(meth)acryloxy-2-hydroxypropyloxy]propylbis(trimethylsiloxy)butylsilane, 3-(meth)acryloxy-2-(2-hydroxyethoxy)-propyloxy)propylbis(trimethylsiloxy)methylsilane. lan, 3-(meth)acryloxy-2-hydroxypropyloxy)propyl tris(trimethylsiloxy)silane, N-[tris(trimethylsiloxy)silylpropyl]-(meth)acrylamide, N-(2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy)propyl)-2-methyl(meth)acrylamide, N-(2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy)propyl)-2-methyl(meth)acrylamide, N-(2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy)propyl)-(meth)acrylamide, N-(2 -Hydroxy-3-(3-(tris(trimethylsilyloxy))silyl)propyloxy)propyl)-2-methylacrylamide, N-(2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl)propyloxy)propyl)(meth)acrylamide, N-[tris(dimethylpropylsiloxy)silylpropyl]-(meth)acrylamide, N-[tris(dimethylphenylsiloxy)silylpropyl](meth)acrylamide, N-[tris(dimethylethylsiloxy)-silylpropyl N,N-bis[2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)-propyloxy)propyl]-2-methyl(meth)acrylamide, N,N-bis[2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy)propyl]-2-methyl(meth)acrylamide, N,N-bis[2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl)propyloxy)propyl]-2-methyl(meth)acrylamide, N,N-bis[2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl)propyloxy)propyl](meth)acrylamide, N-[2-hydroxy-3-(3-(t-butyldimethylsilyl)propyloxy)propyl]-2-methyl(meth)acrylamide, N-[2-hydroxy-3-(3-(t-butyldimethylsilyl)propyloxy)propyl](meth)acrylamide, N,N-bis[2-hydroxy-3-(3-(t-butyldimethylsilyl)propyloxy)propyl]-2-methyl(meth)acrylamide, N-2-(meth)acrylamide 45. The ophthalmic product or method of embodiment 43 or 44, comprising: aryloxyethyl-O-(methyl-bis-trimethylsiloxy-3-propyl)silyl carbamate, 3-(trimethylsilyl)propyl vinyl carbonate, 3-(vinyloxycarbonylthio)propyl-tris(trimethyl-siloxy)silane, 3-[tris(trimethylsiloxy)silyl]propyl vinyl carbamate, 3-[tris(trimethylsiloxy)silyl]propyl allyl carbamate, 3-[tris(trimethylsiloxy)silyl]propyl vinyl carbonate, or combinations thereof. 46. The at least one silicone-containing vinyl monomer is an α-(meth)acryloxypropyl-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-(meth)acryloxy-2-hydroxypropyloxypropyl-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-(2-hydroxyl-methacryloxypropyloxypropyl)-ω-C 1 ~C 4 -Alkyl-decamethylpentasiloxane, α-[3-(meth)acryloxyethoxy-2-hydroxypropyloxypropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-[3-(meth)acryloxy-propyloxy-2-hydroxypropyloxypropyl]-terminated ω-C 1 ~C 4-Alkyl-terminated polydimethylsiloxane, α-[3-(meth)acryloxyisopropyloxy-2-hydroxypropyloxypropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-[3-(meth)acryloxybutyloxy-2-hydroxypropyloxypropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-[3-(meth)acryloxyethylamino-2-hydroxypropyloxypropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-[3-(meth)acryloxypropylamino-2-hydroxypropyloxypropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-[3-(meth)acryloxy-butylamino-2-hydroxypropyloxypropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-(meth)acryloxy(polyethyleneoxy)-2-hydroxypropyloxypropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-[(meth)acryloxy-2-hydroxypropyloxy-ethoxypropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-[(meth)acryloxy-2-hydroxypropyl-N-ethylaminopropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-[(meth)acryloxy-2-hydroxypropyl-aminopropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-[(meth)acryloxy-2-hydroxypropyloxy-(polyethyleneoxy)propyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-(meth)acryloylamidopropyloxypropyl-terminated ω-C1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-N-methyl-(meth)acryloylamidopropyloxypropyl-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-[3-(meth)acrylamidoethoxy-2-hydroxypropyloxy-propyl]-terminated ω-C 1 ~C 4 -Alkyl polydimethylsiloxane, α-[3-(meth)acrylamidopropyloxy-2-hydroxypropyloxypropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-[3-(meth)acrylamidoisopropyloxy-2-hydroxypropyloxypropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-[3-(meth)acrylamidobutyloxy-2-hydroxypropyloxypropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-[3-(meth)acryloylamido-2-hydroxypropyloxypropyl]-terminated ω-C 1 ~C 4 -Alkyl polydimethylsiloxane, α-[3-[N-methyl-(meth)acryloylamido]-2-hydroxypropyloxypropyl]-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, N-methyl-N'-(propyltetra(dimethylsiloxy)dimethylbutylsilane)(meth)acrylamide, N-(2,3-dihydroxypropane)-N'-(propyltetra(dimethylsiloxy)dimethylbutylsilane)(meth)acrylamide, (meth)acryloylamidopropyltetra(dimethylsiloxy)dimethylbutylsilane, α-vinyl carbonate-terminated ω-C 1 ~C 4 -Alkyl-terminated polydimethylsiloxane, α-vinyl carbamate-terminated ω-C 1 ~C 446. The ophthalmic product or method of any one of embodiments 43 to 45, comprising an alkyl-terminated polydimethylsiloxane, or a mixture thereof. 47. The ophthalmic product or method of any one of embodiments 43-46, wherein the silicone hydrogel material comprises repeat units of at least one polysiloxane vinyl crosslinker. 48. The ophthalmic product or method of embodiment 47, wherein the at least one polysiloxane vinyl crosslinker comprises di-(meth)acryloyl-terminated polydimethylsiloxane, divinyl carbonate-terminated polydimethylsiloxane, divinyl carbamate-terminated polydimethylsiloxane; N,N,N',N'-tetrakis(3-methacryloxy-2-hydroxypropyl)-alpha,omega-bis-3-aminopropyl-polydimethylsiloxane, or a combination thereof. 49. The at least one polysiloxane vinyl crosslinker is represented by the formula (I): [ka] (In the formula, provided that υ1 / ω1 is about 0.035 to about 0.15 (preferably about 0.040 to about 0.12, and more preferably about 0.045 to about 0.10), υ1 is an integer of 30 to 500, and ω1 is an integer of 1 to 75; X 01 is O or NR N and R N is hydrogen or C 1 ~C 10 - alkyl; R o is hydrogen or methyl; R I1 and R I2 are each independently a substituted or unsubstituted C 1 ~C 10 an alkylene divalent radical or -R I4 -OR I5 - is a divalent radical of R I4 and R I5 are each independently a substituted or unsubstituted C 1 ~C10 is an alkylene divalent radical; R I3 Formula (Ia) to (Ie) [ka] is one of the monovalent radicals; p1 is zero or 1; m1 is an integer from 2 to 4; m2 is an integer from 1 to 5; m3 is an integer from 3 to 6; m4 is an integer from 2 to 5; R I6 is hydrogen or methyl; R I7 is a C with a valence of (m2+1) 2 ~C 6 is a hydrocarbon radical; R I8 is a C with a valence of (m4+1) 2 ~C 6 is a hydrocarbon radical; R I9 is ethyl or hydroxymethyl; R I10 is methyl or hydromethyl; R I11 is hydroxyl or methoxy; X I1 is a sulfur bond of -S- or -NR I12 - is a tertiary amino bond, R I12 is C 1 ~C 1 alkyl, hydroxyethyl, hydroxypropyl or 2,3-dihydroxypropyl; X I2 teeth, [ka] is an amide bond, and R I13 is hydrogen or C 1 ~C 10 (It is alkyl) 48. The ophthalmic product or method of embodiment 47, comprising a vinyl crosslinker of 50. The at least one polysiloxane vinyl crosslinking agent is represented by the formula (1) to (7): [ka] (In the formula, υ1 is an integer from 30 to 500; υ2 is an integer from 5 to 50; υ3 is an integer from 5 to 100; ω2 and ω3 are each independently an integer from 1 to 15; a1 and g1 are, independently of each other, zero or 1; h1 is an integer from 1 to 20, and h2 is an integer from 0 to 20; m1 and m3 are each independently 0 or 1, m2 is an integer from 1 to 6, m4 is an integer from 1 to 5, and m5 is 2 or 3; q1 is an integer from 1 to 20, q2 is an integer from 0 to 20, q3 is an integer from 0 to 2, q4 is an integer from 2 to 50, and q5 and q6 are each independently a number from 0 to 35, provided that (q4+q5+q6) is an integer from 2 to 50; x+y is an integer between 10 and 30; e1 is an integer of 5 to 100, p1 and b1 are each independently an integer of 0 to 50, provided that if (p1+b1)≧1, then (e1+p1+b1)≧10, and
number
[0137] The above disclosure enables those skilled in the art to carry out the present invention.Various modifications, alterations and combinations can be made to the various embodiments described herein.In order to better enable the reader to understand specific embodiments and their advantages, reference to the following examples is proposed.It is intended that the present specification and examples are considered to be illustrative. EXAMPLES
[0138] Example 1 Measurement of oxygen permeability Unless otherwise specified, oxygen permeability (Dk / t), intrinsic (or edge-corrected) oxygen permeability (Dk i Or Dk c) is determined according to the procedure described in ISO 18369-4.
[0139] Surface wetting test. The water contact angle (WCA) of a contact lens is a common measure of the surface wettability of a contact lens. In particular, a lower water contact angle corresponds to a more wettable surface. The average contact angle (droplet) of a contact lens is measured using a VCA2500XE contact angle measuring instrument from AST, Inc., located in Boston, Massachusetts. This instrument measures the advancing contact angle (θ a ) or receding contact angle (θ r ) or sessile drop (static) contact angles can be measured. Unless otherwise specified, the water contact angle is the sessile drop (static) contact angle on the front surface of the contact lens. Measurements are taken on fully hydrated contact lenses immediately after wiping dry. The wiped dry lens is then mounted front side up on the contact angle measurement platform, and the sessile drop contact angle is measured automatically using the software provided by the manufacturer. The resistivity of deionized water (ultrapure water) used to measure the water contact angle is >18 MΩcm, and the volume of the drop used is 2 μl. The tweezers and platform are thoroughly cleaned with isopropanol and rinsed with deionized water before contacting the contact lens. Each static water contact angle is the average of the left and right water contact angles. The static water contact angle relative to the contact lens is the average water contact angle obtained by averaging the static water contact angles measured on at least five contact lenses.
[0140] Water Break Time (WBUT) Test The surface hydrophilicity of the lenses (after autoclaving) is assessed by measuring the time it takes for the water film to begin to break down on the lens surface. Lenses exhibiting a WBUT ≥ 5 seconds are considered to have a hydrophilic surface and are expected to exhibit sufficient wettability (ability to support a tear film) on the eye.
[0141] Lenses are prepared for drainage measurements by removing the lenses from the blisters (or containers) with soft plastic tweezers (Menicon) and placing them into a beaker containing phosphate buffered saline. The beaker contains at least 20 mL of phosphate buffered saline per lens, with a maximum of three lenses per beaker. After the lenses have soaked for a minimum of 30 minutes and a maximum of 24 hours, the lenses are transferred with soft plastic tweezers into a 96-well plastic tray containing fresh phosphate buffered saline.
[0142] Water break-off time is measured at room temperature as follows: the lens is picked up with soft plastic tweezers as close as possible to the lens edge, with the base curve facing the user, taking care not to let the lens touch the sides of the well after removal from the saline solution. The lens (101) is shaken once to remove excess saline, as shown diagrammatically in FIG. 1, and a timer is started. Ideally, the water film (120) on the base curve surface of the lens will recede in a uniform circular pattern (125) from the point of contact with the tweezers tip (111). The timer is stopped when approximately 30% of the hydration area (125) has receded, and this time is recorded as the water break-off time (WBUT). Lenses that do not show the ideal retraction pattern can be rehydrated for at least 30 seconds, then placed back in the tray and remeasured.
[0143] equilibrium moisture content The equilibrium water content (EWC) of contact lenses is determined as follows: The amount of water (expressed as weight percent) present in hydrated hydrogel contact lenses that have been fully equilibrated with saline is measured at room temperature. The lenses are quickly stacked and after wiping the lenses with a cloth, the stack of lenses is transferred to an aluminum pan on an analytical balance. The number of lenses in each sample pan is typically five. Record the hydrated weight of the pan + lenses. Cover the pan with aluminum foil. Place the pan in a laboratory oven at 100 ± 2 °C and dry for 16-18 hours. Remove the pan + lenses from the oven and cool in a desiccator for at least 30 minutes. Remove one pan from the desiccator and discard the aluminum foil. Weigh the pan + dry lens sample on the analytical balance. Repeat for all pans. The wet and dry weights of the lens samples can be calculated by subtracting the weight of the empty weighing pan.
[0144] Elasticity The elastic modulus of contact lenses is determined using an MTS Insight instrument. The contact lenses are first cut into 3.12 mm wide strips using a Precision Concept two-stage cutter. Five thickness values are measured within a gauge length of 6.5 mm. The strips are attached to the grips of the instrument and submerged in PBS (phosphate buffered saline) at a controlled temperature of 21±2°C. Typically, a 5N load cell is used for testing. A constant force and rate is applied to the sample until it breaks. Force and displacement data are collected by the TestWorks software. The elastic modulus value is calculated by the TestWorks software, which is the slope or tangent of the stress versus strain curve near zero elongation in the elastic deformation region.
[0145] Transmittance A contact lens is manually placed into a specially manufactured sample holder or similar that maintains the shape of the lens as it would be on the eye. The holder is then immersed in a 1 cm path length quartz cell that contains phosphate buffered saline (PBS, pH approximately 7.0-7.4) as a reference. A UV / Visible spectrophotometer such as a Varian Cary 3E UV-Visible spectrophotometer equipped with a LabSphere DRA-CA-302 beam splitter can be used for this measurement. Percent transmission spectra are collected over the wavelength range of 250-800 nm, with %T values collected at 0.5 nm intervals. This data is transferred to an Excel spreadsheet and used to determine whether the lens meets Class 1 UV absorbance. The transmittance is calculated using the following formula: UVA%T=315nm~380nm average % transmittance x 100 UVB%T=280nm~315nm average % transmittance x 100 Violet %T = average % transmittance from 380nm to 440nm x 100.
[0146] Determining the diameter of hydrated contact lenses Figure 2 shows a schematic of common lens dimensions that are typically determined by contact lens manufacturers. Common dimensions include central thickness (CT) (210), anterior sagittal height (ASag) (220), posterior sagittal height (PSag) (240), base curve equivalent (BCE) (250), edge thickness (ET) (260), and diameter (280). Measurements of common lens dimensions can be performed on fully hydrated contact lenses in a wet cell using a low-coherence interferometer similar to that described by Heidemana and Greivenkampin in Optical Engineering 55(3), 034106 (March 2016).
[0147] For the measurements, a contact lens is fixed on the flat bottom surface of a wet cell filled with phosphate-buffered saline, and a motion controller is used to position a low-coherence interferometer at the geometric center of the lens. The interferometer measures the material thickness based on the reflection between different material surfaces. The center of the lens is determined by camera measurements.
[0148] The diameter is defined as the outermost edge of the lens as viewed from above the lens. The edge points are fitted to an ellipse and the diameter is calculated as the average of the long and short ellipse diameters. Typically, contact lenses have a highly circular diameter, and both circular and elliptical fittings will give similar values. However, if the lens is slightly out of round, an ellipse will more accurately represent the shape of the contact lens diameter than a circle. The lens diameters of 3 to 10 contact lenses from a single batch of contact lenses are measured and averaged to obtain the average lens diameter of the contact lenses in that batch.
[0149] 7 cycles of simulated one-day wear extraction Seven cycles of simulated one-day-wear extraction (S1DW extraction) are performed as follows: In the first cycle of S1DW extraction, one to three ready-to-use SiHy contact lenses are removed from their sealed packages and wiped. All wiped ready-to-use SiHy contact lenses are immersed together in 1.0 mL of fresh phosphate-buffered saline (PBS) as extraction medium in one vial that is kept shaking in a 35°C water bath for 24 hours. All PBS used in the first cycle of S1DW extraction is then pipetted out of the vial and saved for later UPLC (ultra-performance liquid chromatography) analysis. In the second to seventh cycles of S1DW extraction, 1.0 mL of free PBS as extraction medium is added to the vial containing the ready-to-use SiHy contact lenses that underwent the preceding cycle of S1DW extraction. The ready-to-use SiHy contact lenses are immersed together in the added 1.0 mL of fresh PBS in a vial that is kept shaking in a 35°C water bath for 24 hours. All PBS used in that cycle of S1DW extraction is then pipetted out of the vial and saved for later UPLC analysis.
[0150] chemicals In the following examples, the following abbreviations are used: TFA stands for trifluoroacetic acid; UPW stands for ultrapure water with a resistivity of >18 MΩcm; UPLC stands for ultra-performance liquid chromatography; NVP stands for N-vinylpyrrolidone; MMA stands for methyl methacrylate; TEGDMA stands for triethylene glycol dimethacrylate; VAZO 64 stands for 2,2'-dimethyl-2,2'azodipropiononitrile; Nobloc stands for 2-[3-(2H-benzotriazol-2-yl)-4-hydroxyphenyl]ethyl methacrylate from Aldrich; UV28 stands for 2-{2'-hydroxy-3'-tert-butyl-5'-[3'-methacryloyloxypropoxy]phenyl}-5-chloro-2H-benzotriazole; RB247 stands for Reactive Blue 247; TAA stands for tert-amyl alcohol; PrOH stands for 1-propanol; IPA stands for isopropanol; PBS has a pH of 7.2±0.2 at 25° C. and contains approximately 0.077% by weight of NaH 2 PO 4 H 2 O and about 0.31% by weight of Na 2 HPO 4 2H 2 % represents weight percent; D9 represents monobutyl terminated monomethacryloxypropyl terminated polydimethylsiloxane (Mw about 984 g / mol from Shin-Etsu); "G4" macromer represents dimethacryloyloxypropyl terminated polysiloxane of formula (A) (Mn about 13.5 Kg / mol, OH content about 1.8 meq / g). [ka]
[0151] Example 2 Preparation of the polymerizable composition Lens formulations (polymerizable compositions), I-IV, are prepared to have the compositions shown in Table 1 (in parts).
[0152] [Table 2]
[0153] The formulation is prepared by combining the listed ingredients in their target amounts in a clean bottle and mixing with a stir bar at 600 rpm for 30 minutes at room temperature. After all solids are dissolved, the formulation is filtered using a 2.7 μm glass microfiber filter.
[0154] Cast molded SiHy contact lenses The lens formulation is purged with nitrogen for 30-35 minutes at room temperature. 2 The purged lens formulation is placed into a polypropylene mold and heat cured in an oven under the following cure conditions: ramp from room temperature to a first temperature and then hold at the first temperature for a first cure time; ramp from the first temperature to a second temperature and hold at the second temperature for a second cure time; optionally ramp from the second temperature to a third temperature and hold at the third temperature for a third cure time; and optionally ramp from the third temperature to a fourth temperature and hold at the fourth temperature for a fourth cure time.
[0155] The lens mold is opened using a demolder with push pins. The lens is pushed into the base curve mold with the push pins, and then the mold is separated into a base curve half mold and a front curve half mold. The base curve half mold with the lens on it is placed into an ultrasonic device (e.g., Dukane single horn ultrasonic device). The dry lens is removed from the mold with a certain energy force. The dry lens is placed into a designed extraction tray. Alternatively, the lens can be removed from the base curve half mold by floating (i.e., without ultrasound, by immersion in an organic solvent, e.g., IPA).
[0156] After removal from the mold, the cast-molded SiHy contact lenses were extracted with PrOH for 180 min to extract the lenses, rinsed with water (55 / 45) for approximately 25 min, and then washed with PB (approximately 0.077 wt. % NaH2 PO 4 H 2 O and about 0.31% by weight Na 2 HPO 4 2H 2 The lenses are rinsed with 0.02% phosphate buffer containing 0 for about 50-60 minutes and then packaged / sealed in polypropylene (PP) lens packaging shells (blisters) with 0.65 mL of packaging solution as described in the Examples below. The sealed lens packages are autoclaved at about 121°C for about 45 minutes. The resulting SiHy contact lenses are characterized according to the procedure as having the following properties: Dkc about 105 barrer to 118 barrer; EWC about 54% to 57%; Elastic modulus about 0.45 MPa to 0.62 MPa; WBUT about 23 sec to 40 sec; Water contact angle with captive bubble about 47° to 52°, friction rating about 2.0.
[0157] In the examples that follow, unless otherwise specified, SiHy contact lenses made from Formulation IV are used.
[0158] Example 3 Preparation of packaging solution Copolymer 845 is a copolymer of N-vinylpyrrolidone and dimethylaminoethyl methacrylate (M by GPC against polyethylene oxide standards). w Approximately 700,000~1,200,000g / mol, M w / M n Approximately 5.7 to 8.5) and is obtained from your ISP.
[0159] R is methyl, the average value of m is 45, and the average value of n is 10. 45 BO 10 ") is prepared according to the procedure described in U.S. Pat. No. 8,318,144. This polymeric surfactant has an HLB of about 14.7 and has the formula:
number
[0160] Four packaging solutions are prepared by dissolving the various components shown in Table 2 in 1 L of water. Concentrations are in weight percent.
[0161] [Table 3]
[0162] Lens packaging The SiHy contact lenses prepared in Example 2 are individually packaged and sealed in PP blister packages, each containing 0.65 mL of a packaging solution (one of the packaging solutions I-IV prepared above). The sealed lens packages are autoclaved at about 121° C. for 45 minutes.
[0163] Wettability of ready-to-use SiHy contact lenses After approximately 12 months of storage at room temperature, the static water contact angle (WCA) of ready-to-use SiHy contact lenses taken directly out of the package was OOP ) is determined according to the procedure described in Example 1. The results are reported in Table 3.
[0164] [Table 4]
[0165] Table 3 shows the results of the polymer surfactant (EO 45 BO 10 The wettability of ready-to-use SiHy lenses packaged in a packaging solution containing EO 2000 and autoclaved and then stored at room temperature for approximately 12 months was45 BO 10 EO (Comparative Packaging Solution I) and that, although Copolymer-845 alone can slightly improve the wettability of the ready-to-use SiHy lenses packaged in the packaging solution containing Copolymer-845, the wettability of the ready-to-use SiHy lenses packaged in the packaging solution containing Copolymer-845 is significantly improved compared to the ready-to-use SiHy lenses packaged in the packaging solution containing Copolymer-845 (Comparative Packaging Solution I). 45 BO 10 The combination of EO and a high molecular weight hydrophilic polymer (Copolymer-845) 45 BO 10 This indicates that the present invention can have some synergistic effect in lowering the water contact angle (i.e., improving the wettability) of ready-to-use SiHy lenses packaged in a packaging solution containing a mixture of Copolymer-845 and Copolymer-845.
[0166] Example 4 The effective time of polymeric surfactants in ready-to-use SiHy contact lenses was measured using fluorescently labeled polymeric surfactants (NBD-labeled (EO 45 BO 10 , NBD is nitrobenzoxadiazole and EO 45 BO 10 is a PEO-PBO block copolymer of formula (S2), R is methyl, the average value of m is 45, and the average value of n is 10) (EO 45 BO 10 The amount of surfactant present in the contact lens is estimated using a fluorescent label (NBD) that allows for confocal visualization of the polymeric surfactant within the contact lens, demonstrating that the polymeric surfactant remains present after seven cycles of simulated daily wear and wash-extraction (i.e., mimicking a seven-day daily wear and wash routine).
[0167] NBD-EO 45 BO 10 Synthesis of NBD-EO 45 BO 10 is prepared according to the following scheme: [ka]
[0168] 100 mg of NBD-COCl (4-(N-chloroformylmethyl-N-methylamino)-7-nitro-2,1,3-benzoxadiazole) is dissolved in 0.5 mL of hexane and 2.5 mL of methylene chloride. Then, about 1 g of EO is added. 45 BO 10 (Mn approx. 3000g / mol) and 0.7g of dry K 2 CO 3 The reaction is then cooled to room temperature. 2 The incubation was carried out at room temperature for at least 48 hours under K 2 CO 3 Centrifuge and evaporate the solvent. 45 BO 10 The purification of NBD-EO is performed using dialysis or SEC column. 45 BO 10 Further purification is performed by HPLC column fraction collection to obtain 99.5% by weight.
[0169] The HLB of this NBD-labeled polymeric surfactant is about 13.4, calculated based on the following formula:
number
[0170] Preparation of packaging solution The packaging solution was prepared using the purified NBD-EO 45 BO 10Dissolve NBD-O, Copolymer 845, and other necessary ingredients in water to obtain the following composition: 150 ppm NBD-O 45 BO 10 , 1 wt% copolymer 845, 0.77 wt% NaCl, 0.076 wt% NaH 2 PO 4 H 2 O, and 0.47% by weight Na 2 HPO 4 7H 2 Prepare to have O.
[0171] Lens packaging The SiHy contact lenses prepared according to the procedure described in Example 2 are individually packaged and sealed in PP blister packages each containing 0.65 mL of the prepared packaging solution. The sealed lens packages are autoclaved at about 121° C. for 45 minutes.
[0172] NBD-EO 45 BO 10 Import NBD-EO in packaging solution before and after autoclaving 45 BO 10 The concentration is measured by HPLC.
[0173] NBD-EO in packaging solution 45 BO 10 The analysis is performed using a reversed-phase Waters UPLC system equipped with a fluorescence detector and a 150 x 2.1 mm diameter, 1.9 μm particle size UPLC column (e.g., ThermoScientific Hypersil GOLD). The mobile phase is prepared as a mixture of Mobile Phase A-50:30:19.8:0.2 (v / v) methanol / acetonitrile / water / formic acid and Mobile Phase B-59.8:40:0.2 (v / v) methanol / acetone / formic acid. The mobile phase is filtered through a 0.45 μm nylon filter. The flow rate is 0.3 mL per minute. The column temperature is set at 60 °C. The analysis time is 30 min. Fluorescent NBD-EO 45 BO 10(excitation λ = 460 nm; emission λ = 510 nm) is detected in the retention time (RT) range from 4 min to RT 12 min.
[0174] NBD-EO incorporated into ready-to-use SiHy 45 BO 10 The amount of (C before autoclave -C after autoclave )*Calculated at 0.65mL. NBD-EO incorporated into ready-to-use SiHy contact lenses 45 BO 10 Use five ready-to-use lenses to obtain an average amount of NBD-EO 45 BO 10 The uptake is determined to be approximately 100 μg / lens.
[0175] In addition, NBD-EO incorporated into ready-to-use SiHy contact lenses 45 BO 10 The amount of NBD-EO in the extraction medium was determined by completely extracting it with a 1:1 mixture of acetone / hexane as the extraction medium. 45 BO 10 Similarly, the amount of NBD-EO incorporated in a ready-to-use SiHy contact lens can be determined by determining the amount of NBD-EO incorporated in the ready-to-use SiHy contact lens. 45 BO 10 To obtain an average amount of 5 ready-to-use lenses are used.
[0176] NBD-EO 45 BO 10 Visualization of uptake NBD-EO incorporated into ready-to-use SiHy contact lenses 45 BO 10 The results are visualized by confocal microscopy. As a control, SiHy contact lenses that were not subjected to the autoclaving step and were immersed in the packaging solution are also examined by confocal microscopy. 45 BO 10 When examining SiHy contact lenses autoclaved in 5% CO (without CO), note the absence of fluorescence to serve as baseline fluorescence.
[0177] Ready-to-use SiHy contact lenses and control lenses are cross-sectioned orthogonally and imaged using a Nikon fluorescence microscope. 45 BO 10 Select a 488 nm laser to excite the NBD-EO. A magnification of 63x is used in this experiment. The scale bar is 50 μm. Fluorescence images of the lens cross section of the ready-to-use SiHy contact lens are shown in Fig. 1. 45 BO 10 This shows that the EO is adsorbed onto the lens surface and penetrates deep into the bulk material of the ready-to-use SiHy contact lens (Figure 3A). In contrast, the control contact lens NBD-EO 45 BO 10 The fluorescence image of the lens cross section is shown in Fig. 1. 45 BO 10 The results show that most of the α-aminobutyric acid is adsorbed onto the lens surface and penetrates into the bulk material of the surface region of the contact lens (Figure 4A). Confocal microscopy line scans (Figures 3B and 4B) confirm the visual observations.
[0178] These experiments showed that significant amounts of NBD-EO 45 BO 10 is located in the surface and near-surface regions, indicating that the autoclaving step is important for the incorporation of the polymeric surfactant deep into the SiHy contact lens.
[0179] 7 cycles of simulated daily wear and cleaning extraction Seven cycles of simulated daily wear and wash extraction (S1DWC extraction) are performed as follows: In cycle 1, each lens is removed from the sealed package, wiped, and then immersed in 1 mL of fresh PBS in a vial that is kept shaking in a 35°C water bath for 8 hours. After 8 hours of soaking, the lens is gently wiped and soaked in 2 mL of fresh Opti-Free Refill (OFR) solution in a vial for 16 hours at room temperature. In cycle 2, the lens is removed from the OFR solution used in cycle 1, gently wiped again, and soaked in 1 mL of fresh PBS in a vial that is kept shaking in a 35°C water bath for 8 hours. After 8 hours of soaking, the lens is gently wiped and soaked in 2 mL of fresh OFR in a vial for 16 hours at room temperature. In cycles 3 to 6, extraction is performed as in cycle 2. In the seventh cycle, the lenses are removed from the OFR solution used in the sixth cycle, gently wiped again, and immersed in 1 mL of fresh PBS in a vial that is kept shaking in a 35°C water bath for 8 hours. They are not immersed in the OFR solution in the seventh cycle.
[0180] All PBS and OFR solutions after soaking are stored in the freezer until HPLC injection.
[0181] It should be pointed out that the soaking of one SiHy contact lens in 1 mL of fresh PBS at 35° C. for 8 hours is intended to simulate the normal daily wearing of a contact lens on the eye by a patient (approximately 8 hours), whereas the soaking of one SiHy contact lens in 2 mL of OFR is intended to simulate the daily practice of a patient following a normal lens care regime.
[0182] NBD-EO 45 BO 10The lenses after autoclaving with are butterfly cut and imaged using a Nikon conventional microscope at time 0 and after 7 cycles of simulated 1 day wear and wash-extraction. The amount of fluorescence is estimated by integration using the image analysis software ImageJ. The results show that at least about 70% of the fluorescence remains in the contact lenses after 7 days.
[0183] Table 4 shows the amount of NBD-EO in each extraction medium as determined by the HPLC method described above. 45 BO 10 The results of the release of
[0184] [Table 5]
[0185] The results in Table 4 show that the ready-to-use SiHy contact lenses of this example have a NBD-EO concentration of at least 3.1 μg / lens / 8 hours, or 0.00646 μg / lens / min. 45 BO 10 At a normal average tear volume of 6.2 ± 2.0 μL (S. Mishima et al., Invest. Ophthalmol. Vis. Sci. 1966, 5: 264-276), the release rate of the polymer surfactants described above resulted in a release rate of 0.00646 μg min−1 in the tear fluid of the eye. -1 / 6.2μL=1.04μg / mL of polymeric surfactant concentration is obtained.
[0186] Example 5 This example shows seven cycles of simulated one-day wear extraction.
[0187] Preparation of packaging solution The packaging solution was prepared in Example 3 above using purified EO-PBO block copolymer having formula (S2) (R is methyl, the average value of m is 45, and the average value of n is 10). 45 BO 10ISP Copolymer 845 (M against polyethylene oxide standards by GPC) w Approximately 700,000~1,200,000g / mol, M w / M n Prepare by dissolving in water the following components: 150 ppm EO, ... 45 BO 10 , 1 wt% Copolymer 845, 0.77 wt% NaCl, 0.076 wt% NaH 2 PO 4 H 2 O, and 0.47% by weight Na 2 HPO 4 7H 2 O.
[0188] Lens packaging The SiHy contact lenses prepared in Example 2 are individually packaged and sealed in PP blister packages each containing 0.65 mL of the above prepared packaging solution. The sealed lens packages are autoclaved at about 121° C. for 45 minutes.
[0189] EO incorporated into ready-to-use SiHy contact lenses 45 BO 10 The amount of (C before autoclave -C after autoclave )*0.65mL. before autoclave EO in the packaging solution before autoclaving 45 BO 10 was determined to be 150 ppm; after autoclave EO in the packaging solution after autoclaving 45 BO 10 The concentration of EO incorporated in the ready-to-use SiHy lens was determined to be 84-91 ppm. 45 BO 10 The amount is determined to be 38-43 μg / lens.
[0190] UPLC method The UPLC analysis is performed on a Waters H-Class system equipped with an ELSD (Evaporative Light Scattering Detector) and a PDA (Photodiode Array Detector) using a column heater or equivalent. The column is 5 μm C-4300 Å; 50 mm x 4.6 mm (e.g. Phenomenex Jupiter or equivalent) and the software is Empower3. The ELSD detector is EO with the following settings: 45 BO 10 The detector is for detecting Copolymer 845 at a UV wavelength of 227 nm. The injection volume is 250.0 μL. The sample compartment temperature is set at 25° C. The column conditions are: column temperature: 60° C.; pressure: approximately 2000 PSI. Mobile phase A is 0.5 M ammonium formate; mobile phase B is 0.04% TFA (trifluoroacetic acid) / methanol. The run time is 30 minutes.
[0191] System compatibility was determined using 1.0% Co-845 and 150 ppm EO. 45 BO 10 The peak areas are verified by calculating the %RSD (relative standard deviation) of the first five target concentrations of injections. The %RSDs for each analyte are all less than 1.0%, below the maximum valid specification of 10%. The peak positions are also within the specification for 1 minute retention time variation.
[0192] Samples for UPLC analysis are prepared as follows: For the analysis of each extraction medium used in each of the seven cycles, the solvent (water) is evaporated and the polymeric surfactant (EO 45 BO 10 ) material is redissolved in 500 μL of UPW for UPLC analysis.
[0193] Those skilled in the art will appreciate that by using smaller volumes of UPW (eg, 0.25 mL) in the UPLC sample preparation, the concentration of polymeric surfactant can be increased, thereby increasing analytical precision.
[0194] For analysis of each extraction medium used in each of the seven cycles, the solvent (PBS or OFR) for UPLC analysis is directly injected.
[0195] 7 cycles of aqueous extraction for 24 hours After storing the sealed and autoclaved lens packages at room temperature for approximately 12 months, 7 cycles of 24-hour aqueous extraction of SiHy contact lenses are performed as follows: In the first cycle, 10 lenses each are removed from the sealed package, wiped, and then the 10 wiped lenses are immersed together in 2 mL of fresh PBS (or water for comparison only in this example) in a vial that is kept shaking in a 35°C water bath for 24 hours. In the second cycle, all of the PBS (or water) used in the first cycle is pipetted out of the vial and saved for later UPLC analysis. 2 mL of fresh PBS (or water) is added to the vial, and then the 10 lenses are kept shaking in a water bath for immersion at 35°C for 24 hours. In cycles 3 to 7, extraction is performed as in cycle 2. All extraction media (PBS or water) after immersion are stored in a freezer until UPLC analysis.
[0196] EO released per ready-to-use SiHy lens 45 BO 10 Amount of (W released ) is calculated as follows:
number
[0197] [Table 6]
[0198] Ten lenses released into 2 mL of PBS contained approximately 35.8–38 μg of EO in each lens after seven cycles of 24-h aqueous extraction. 45 BO 10 remains.
[0199] It was found that no detectable amounts of Copolymer-845 were released by the ready-to-use SiHy contact lenses, suggesting that Copolymer-845 may not have been able to penetrate into the SiHy lenses during autoclaving and bind to the surface in sufficient amounts to be released into the extraction medium during the first cycle.
[0200] In addition, ready-to-use SiHy lenses exhibit better EO adhesion in PBS than in water at 35°C. 45 BO 10 It was also found that PBS can release a large amount of PBS. PBS is selected as the extraction medium to be used in the subsequent 7 cycles of simulated 1-day wear (S1DW) extraction.
[0201] In addition, the EO released in the extraction medium in the first cycle 45 BO 10 was found to be significantly higher than in the extraction media of the other cycles, suggesting that the polymeric surfactants located in the surface and subsurface regions are released into the extraction media in the first cycle.
[0202] 7 cycles of simulated one-day wear extraction In this example, after storing the sealed and autoclaved lens packages at room temperature for approximately 12 months, seven cycles of S1DW extraction of SiHy contact lenses are carried out according to the procedure described in Example 1, except that one lens is used. All PBS as extraction medium after each cycle of S1DW extraction is stored in a freezer until UPLC analysis. The sealed lens packages are
[0203] EO released per ready-to-use SiHy lens 45 BO 10 Amount of (W released ) is calculated as follows:
number
[0204] [Table 7]
[0205] Table 7 shows that after seven cycles of S1DW extraction, approximately 27.8 μg of EO was present in each lens. 45 BO 10The results indicate that the Copolymer-845 remains in the SiHy contact lenses and that the ready-to-use SiHy contact lenses are unable to release detectable amounts of Copolymer-845, suggesting that the Copolymer-845 may not have been able to penetrate into the SiHy lenses during autoclaving and bind to the surface in sufficient amounts to be released into the extraction medium in the first cycle. 45 BO 10 The amount of was significantly higher than that of the extraction media of the other cycles, suggesting that the polymeric surfactants at the surface and just below the surface region were released into the extraction media in the first cycle.
[0206] Example 6 Preparation of packaging solution The five packaging solutions were prepared using purified EO-PBO block copolymers having the formula (S2) (where R is methyl, the average value of m is 45, and the average value of n is 10) as prepared in Example 3 above. 45 BO 10 ISP Copolymer 845 (polyethylene oxide standard) by GPC w Approximately 700,000~1,200,000g / mol, M w / M n Prepare the solution by dissolving in water (approximately 5.7-8.5%) and other ingredients required to have the following composition: EO in one of five different concentrations (50 ppm, 100 ppm, 150 ppm, 250 ppm, and 400 ppm). 45 BO 10 , 1 wt% copolymer 845, 0.77 wt% NaCl, 0.076 wt% NaH 2 PO 4 H 2 O, and 0.47% by weight Na 2 HPO 4 7H 2 O.
[0207] Lens packaging Two types of SiHy lenses: a SiHy contact lens made according to the procedure described in Example 2 and a plasma-treated SiHy contact lens having an equilibrium water content (EWC) of about 33% by weight and made according to the procedure described in Example 3 of US Pat. No. 9,829,723, are individually packaged and sealed in PP blister packages each containing 0.65 mL of one of the five packaging solutions prepared above. The sealed lens packages are autoclaved at about 121° C. for 45 minutes. The following investigations and characterizations are performed on the resulting autoclaved lenses in the sealed lens packages. The sealed and autoclaved lens packages are stored at room temperature for less than three weeks before the tests described below.
[0208] 7 cycles of simulated one-day wear extraction Seven cycles of S1DW extraction of freshly made SiHy contact lenses (storage time at room temperature is less than about 3 weeks) are carried out according to the procedures described in Example 5. As in Example 5, in this example one lens is used in seven cycles of S1DW extraction.
[0209] Change in lens diameter after 7 cycles of S1DW extraction The lens diameter is determined according to the procedure described in Example 1. Control lenses, SiHy contact lenses made according to the procedure described in Example 2, individually sealed and autoclaved in PBS in PP blister packages each containing 0.65 mL of PBS, had an average lens diameter (DIA) of 14.04 ± 0.02 mm. control The test SiHy contact lenses, made according to the procedure described in Example 2, sealed and autoclaved in one of the five packaging solutions prepared above in a lens package, were determined to have lens diameter values (DIA) directly out of the package. OOP ) (reported in Table 7) and lens diameter (DIA) after 7 cycles of S1DW extraction 7S1DW extraction ) is determined to have
[0210] [Table 8]
[0211] The result is a 54% EWC and EO 45 BO 10 This shows that the lens diameter of SiHy contact lenses that are uncoated before autoclaving in a packaging solution containing EO can be increased after autoclaving. 45 BO 10 can penetrate into SiHy contact lenses, and EO 45 BO 10 This suggests that the hydroxypropyl ester can be distributed within the polymer matrix during autoclaving in a packaging solution containing
[0212] The results also show that the lens diameter of the ready-to-use SiHy contact lenses of the present invention can be reduced after seven cycles of S1DW extraction (i.e., roughly corresponding to seven days of continuous wear), which is consistent with the results of the EO 45 BO 10 has not been clearly captured, suggesting that it is distributed in the polymer matrix of the ready-to-use SiHy contact lens of the present invention and may be released into the tear fluid when the lens is worn on the eye.
[0213] Example 7 Preparation of packaging solution Copolymer 845 (polyethylene oxide standard) M by GPC w Approximately 700,000~1,200,000g / mol, M w / M n The copolymer EO, which is a polymeric surfactant having the formula (S2) PEO-PBO block copolymer (R is methyl, the average value of m is 45, and the average value of n is 10), is obtained from ISP. 45 BO 10 is prepared according to the procedure described in US Pat. No. 8,318,144.
[0214] Four packaging solutions (packaging solutions I-IV) are prepared according to the procedure described in Example 3 by dissolving the various components in water as shown in Table 2.
[0215] Lens packaging The SiHy contact lenses made in Example 2 are individually packaged and sealed in PP blister packages containing 0.65 mL of Packaging Solution III or IV (prepared above), respectively, or in vials containing about 2 mL of Packaging Solution I or II (prepared above), respectively. The sealed lens packages are autoclaved at about 121° C. for about 45 minutes. The sealed and autoclaved lens packages are stored at room temperature for less than 3 weeks before testing as described below.
[0216] 7 cycles of simulated one-day wear extraction Seven cycles of S1DW extraction of freshly made SiHy contact lenses (storage time at room temperature is less than about 3 weeks) are performed according to the procedures described in Example 5. As in Example 5, in this example, one lens is used for 7 cycles of S1DW extraction.
[0217] Wettability of ready-to-use SiHy contact lenses Static Water Contact Angle (WCA) of ready-to-use SiHy contact lenses directly from the package OOP ) and the static water contact angle (WCA) of the ready-to-use SiHy contact lens after 7 cycles of S1DW extraction. 7_S1DW ) is determined according to the procedure described in Example 1. The results are reported in Table 8.
[0218] [Table 9]
[0219] All publications, patents and patent application publications cited above in this application are hereby incorporated by reference in their entirety.
Claims
1. 1. A method of making an ophthalmic product comprising a sealed, autoclave sterilized package containing a post-autoclaving packaging solution and a ready-to-use silicone hydrogel contact lens immersed therein, said ready-to-use silicone hydrogel contact lens comprising at least 25 μg / lens of a polymeric surfactant, said polymeric surfactant comprising at least one hydrophilic poly(oxyethylene) segment and at least one hydrophobic poly(oxybutylene) segment, having an HLB value of 11-16 and a number average molecular weight of 800-20,000 Daltons, physically distributed within a polymer matrix of said ready-to-use silicone hydrogel contact lens, a) obtaining a preformed silicone hydrogel contact lens having no coating thereon resulting from an energetic surface treatment that is a plasma, the preformed silicone hydrogel contact lens being free of said polymeric surfactant, the preformed silicone hydrogel contact lens having an equilibrium water content of 38% to 80% by weight, an elastic modulus of 0.2 MPa to 1.5 MPa, and an oxygen permeability of at least 50 barrers; b) placing said preformed silicone hydrogel contact lens in a container containing a pre-autoclaved packaging solution, said pre-autoclaved packaging solution being a buffered saline solution having a pH of from 6.0 to 8.0 and containing a polymeric surfactant, said polymeric surfactant being present in said pre-autoclaved packaging solution in an amount of from 0.009% to 0.032% by weight; (i) at least 25 μg / lens of said polymerized surfactant permeates said preformed silicone hydrogel contact lens during said autoclaving and then diffuses into the polymer matrix of the resulting ready-to-use silicone hydrogel contact lens after autoclaving; and (ii) the difference in lens diameter between said ready-to-use silicone hydrogel contact lens and a control lens which is a preformed silicone hydrogel contact lens autoclaved in phosphate buffered saline without said polymeric surfactant is less than 0.20 mm; A step selected to ensure c) sealing the container to obtain a sealed package containing the ready-to-use silicone hydrogel contact lens immersed in the autoclaved packaging solution; and d) autoclaving the sealed package containing the preformed silicone hydrogel contact lens for at least 30 minutes to infiltrate and physically disperse at least 25 μg / lens of the polymeric surfactant within the polymer matrix of the ready-to-use silicone hydrogel contact lens during autoclaving, wherein the ready-to-use silicone hydrogel contact lens has a capacity to release the polymeric surfactant in an amount of at least 0.2 μg / lens / 24 hours as measured in an aqueous extraction process consisting of seven cycles of simulated one-day-wear extraction, the capacity to release the polymeric surfactant being the amount of the polymeric surfactant released per lens over 24 hours into the extraction medium used in the last cycle of the seven cycles of simulated one-day-wear extraction, and the ready-to-use silicone hydrogel contact lens has a first static water contact angle, WCA, of less than or equal to 75° as measured by the Sessile Drop Method directly removed from the sealed package. OOP and a second static water contact angle of 85° or less measured by the sessile drop method immediately after seven cycles of the simulated one-day wear extraction, WCA 7_S1DW The further step of A method for producing an ophthalmic product comprising:
2. 2. The method of claim 1, wherein the ready-to-use silicone hydrogel contact lens has the ability to release the polymeric surfactant in an amount of at least 0.4 μg / lens / 24 hours as measured in an aqueous extraction process consisting of 7 cycles of the simulated daily wear extraction.
3. 3. The method according to claim 1 or 2, wherein the polymeric surfactant is a diblock copolymer called PEO-PBO or a triblock copolymer called PEO-PBO-PEO or PBO-PEO-PBO, where PEO represents a poly(oxyethylene) segment and PBO represents a poly(oxybutylene) segment.
4. The method according to any one of claims 1 to 3, wherein the polymeric surfactant is a diblock copolymer of formula (S1): _______________ m () n ()) wherein R is selected from the group consisting of hydrogen, methyl, ethyl, propyl, and butyl; EO is ethylene oxide-C 2 H 4 O-; BO is butylene oxide -C 4 H 8 O-; m is an integer having an average value from 10 to 250; n is an integer having an average value from 5 to 125, provided that the value of m / n is from 2:1 to 10:
1.
5. The method according to any one of claims 1 to 4, wherein the polymeric surfactant is a diblock copolymer of formula (S2): 【Chemistry 1】 wherein R is selected from the group consisting of hydrogen, methyl, ethyl, propyl, and butyl; m is an integer having an average value from 10 to 250; and n is an integer having an average value from 5 to 125, provided that the value of m / n is from 2:1 to 10:
1.
6. The method of any one of claims 1 to 5, wherein the ready-to-use silicone hydrogel contact lenses comprise at least 40 μg / lens of polymeric surfactant.
7. The method of any one of claims 1 to 6, wherein the pre-autoclaved packaging solution further comprises 0.1% to 2% by weight of a hydrophilic polymer having a number average molecular weight of at least 100,000 Daltons.
8. 8. The method of claim 7, wherein the hydrophilic polymer is polyvinylpyrrolidone or a copolymer of N-vinylpyrrolidone and at least one amino-containing vinyl monomer selected from the group consisting of alkylaminoalkyl methacrylates having 8 to 15 carbon atoms, alkylaminoalkyl acrylates having 7 to 15 carbon atoms, dialkylaminoalkyl methacrylates having 8 to 20 carbon atoms, dialkylaminoalkyl acrylates having 7 to 20 carbon atoms, and N-vinylalkylamides having 3 to 10 carbon atoms.
9. The method of any one of claims 1 to 8, wherein the preformed silicone hydrogel contact lenses are essentially wettable silicone hydrogel contact lenses.
10. 10. The method of any one of claims 1 to 9, wherein the preformed silicone hydrogel contact lens is comprised of a silicone hydrogel material comprising: (1) repeating units of at least one silicone-containing vinyl monomer and / or repeating units of at least one polysiloxane vinyl crosslinker; and (2) repeating units of at least one hydrophilic vinyl monomer, wherein the at least one silicone-containing vinyl monomer is selected from the group consisting of vinyl monomers having bis(trialkylsilyloxy)alkylsilyl groups, vinyl monomers having tris(trialkylsilyloxy)silyl groups, polysiloxane vinyl monomers, 3-methacryloxypropylpentamethyldisiloxane, t-butyldimethyl-siloxyethyl vinyl carbonate, trimethylsilylethyl vinyl carbonate, and trimethylsilylmethyl vinyl carbonate, and combinations thereof.
11. The silicone hydrogel material comprises repeating units of at least one polysiloxane vinyl crosslinker, the at least one polysiloxane vinyl crosslinker having the formula (I): 【Chemistry 2】 (In the formula, υ1 is an integer between 30 and 500, and ω1 is an integer between 1 and 75, provided that ω1 / υ1 is between 0.035 and 0.15; X 01 is O or NR N and R N is hydrogen or C 1 ~C 10 - alkyl; R o is hydrogen or methyl; R I1 and R I2 are each independently a substituted or unsubstituted C 1 ~C 10 an alkylene divalent radical or -R I4 -O-R I5 - divalent radical, R I4 and R I5 are each independently a substituted or unsubstituted C 1 ~C 10 an alkylene divalent radical; R I3 is represented by the formula (Ia) to (Ie) 【Chemistry 3】 is one of the monovalent radicals p1 is zero or 1; m1 is an integer from 2 to 4; m2 is an integer from 1 to 5; m3 is an integer from 3 to 6; m4 is an integer from 2 to 5; R I6 is hydrogen or methyl; R I7 is C having a valence of (m2+1) 2 ~C 6 is a hydrocarbon radical; R I8 is C having a valence of (m4+1) 2 ~C 6 is a hydrocarbon radical; R I9 is ethyl or hydroxymethyl; R I10 is methyl or hydromethyl; R I11 is hydroxyl or methoxy; X I1 is a sulfur bond of -S- or -NR I12 - is a tertiary amino bond, and R I12 is C 1 ~C 1 alkyl, hydroxyethyl, hydroxypropyl, or 2,3-dihydroxypropyl; X I2 teeth, 【Chemistry 4】 is an amide bond of I13 is hydrogen or C 1 ~C 10 is alkyl) The method of claim 10, comprising a vinyl crosslinker of
12. The silicone hydrogel material comprises repeating units of at least one polysiloxane vinyl crosslinker, the at least one polysiloxane vinyl crosslinker being represented by the formulas (1) to (7): 【number】 (In the formula, υ1 is an integer from 30 to 500; υ2 is an integer from 5 to 50; υ3 is an integer from 5 to 100; ω2 and ω3 are, independently of each other, integers from 1 to 15; a1 and g1 are independently zero or 1; h1 is an integer from 1 to 20, and h2 is an integer from 0 to 20; m1 and m3 are each independently 0 or 1, m2 is an integer from 1 to 6, m4 is an integer from 1 to 5, and m5 is 2 or 3; q1 is an integer from 1 to 20, q2 is an integer from 0 to 20, q3 is an integer from 0 to 2, q4 is an integer from 2 to 50, and q5 and q6 are each independently a number from 0 to 35, provided that (q4+q5+q6) is an integer from 2 to 50; x+y is an integer from 10 to 30; e1 is an integer from 5 to 100, p1 and b1 are each independently an integer from 0 to 50, provided that if (p1+b1)≧1, then (e1+p1+b1)≧10; and [0010] provided that; R o is H or methyl; R 1 , R 1n , R 2n , R 3n and R 4n are each independently H or C having 0 to 2 hydroxyl groups 1 ~C 4 is alkyl; R n5 is H or C 1 ~C 10 is alkyl; R 2 is C 4 ~C 14 is a hydrocarbon divalent radical of the formula: R 3 is C 2 ~C 6 an alkylene divalent radical; R 4 and R 5 are, independently of each other, C 1 ~C 6 an alkylene divalent radical, or C 1 ~C 6 Alkylene-oxy-C 1 ~C 6 an alkylene divalent radical; R 6 and R 7 are, independently of each other, C 1 ~C 6 An alkylene divalent radical or C 1 ~C 6 Alkoxy-C 1 ~C 6 an alkylene divalent radical; R 8 and R 9 are each independently a substituted or unsubstituted C 1 ~C 12 an alkylene divalent radical; X o , X 1 ', X o1 , X 02 and X 03 are each independently O or NR 1 and X 1 , O, NR 1 , NHCOO, OCONH, CONR 1 Or NR 1 CO; X o4 is -COO- or -CONR n5 - and X o5 and X o7 are each independently a direct bond, -COO- or -CONR n5 - and X o6 is a direct bond, C 1 ~C 6 Alkylene divalent radical, C 1 ~C 6 Alkyleneoxy divalent radical, -COO- or -CONR n5 - and X o8 is a direct bond or -COO-; X o9 is O or NR n5 and X 10 is a direct bond, C 1 ~C 6 An alkylene divalent radical, -COO- or -CONR n5 - and E 1 'teeth, 【number】 is a monovalent radical of E 2 teeth, 【number】 is a monovalent radical of E 3 teeth, 【number】 is a monovalent radical of E 4 teeth, 【number】 is a monovalent radical of L 1 is C 2 ~C 8 an alkylene divalent radical, or 【number】 is a divalent radical of L 1 ' is a C having 0 or 1 hydroxyl group 2 ~C 8 an alkylene divalent radical; L 1 " is a C having 0 or 1 hydroxyl group 3 ~C 8 an alkylene divalent radical; L 3 teeth, 【number】 is a divalent radical of P.E. 【number】 is a divalent radical of L 3 ' is C 3 ~C 8 an alkylene divalent radical; L 4 teeth, 【number】 is a divalent radical of hpl 1 teeth, 【number】 is a divalent radical of hpl 2 teeth, 【number】 is a divalent radical of hpl 3 teeth, 【number】 is a divalent radical of hpl 4 teeth, 【number】 is a divalent radical of pOAlk is 【number】 is a divalent radical of EO is an oxyethylene unit (-CH 2 CH 2 O-), PO is an oxypropylene unit 【number】 where BO is an oxybutylene unit. 【number】 and M 0 is C 3 ~C 8 an alkylene divalent radical; M 1 is C 4 ~C 14 is a hydrocarbon divalent radical; M 2 and M. 3 are, independently of each other, C 1 ~C 6 an alkylene divalent radical; J 0 is a C having 0 to 2 hydroxyl or carboxyl groups 1 ~C 12 is a hydrocarbon radical; G1 is a direct bond, C 1 ~C 4 an alkylene divalent radical, or 【number】 is a divalent radical of Here, M o is bonded to a Si atom, and X 04 ~X 10 is -CH in formula (7). 2 - group, and J of formula (7) 0 and at least one of G1 is a hydroxyl group, a urethane bond of -OCONH-, -NHR o at least one moiety selected from the group consisting of an amino group, an amino bond of -NH-, an amide bond of -CONH-, a carboxyl group, and combinations thereof; G 2 is C 1 ~C 4 an alkylene divalent radical, or 【number】 is a divalent radical of G 3 teeth, 【number】 is a divalent radical of wherein h3 and h4 are, independently of each other, 1 or 0; G4 is (a)-NR 3 '-(in the formula, R 3 ' is hydrogen or C 1 ~C 3 alkyl), (b) 【number】 , (c) -NR 0 -G 5 -NR 0 - (in the formula, G 5 is C 1 ~C 6 alkylene divalent radical, 2-hydroxylpropylene divalent radical, 2-(phosphonyloxy)propylene divalent radical, 1,2-dihydroxyethylene divalent radical, 2,3-dihydroxybutylene divalent radical, and (d) -O-G 6 -O-, in the formula, G 6 is C 1 ~C 6 an alkylene divalent radical, 【number】 Divalent radical of (Wherein, h4' is 1 or 2); 【number】 A divalent radical of 【number】 Divalent radical of (Wherein, h5 is 1 to 5). 【number】 Divalent radical of (wherein h6 is 2 or 3), or a substituted C having a hydroxyl group or a phosphonyloxy group. 3 ~C 8 any one of the divalent radicals of an alkylene divalent radical; Y 1 is C 1 ~C 6 Alkylene divalent radical, 2-hydroxylpropylene divalent radical, 2-(phosphonyloxy)propylene divalent radical, 1,2-dihydroxyethylene divalent radical, 【number】 or 【number】 is a divalent radical of Y 2 teeth, 【number】 is a divalent radical of Y 3 teeth, 【number】 is a divalent radical of Z 0 is a direct bond or C 1 ~C 12 an alkylene divalent radical; Z 1 is C 1 ~C 6 Alkylene divalent radical, hydroxy or methoxy substituted C 1 ~C 6 an alkylene divalent radical or a substituted or unsubstituted phenylene divalent radical, Z 2 is C 1 ~C 6 Alkylene divalent radical, hydroxyl or methoxy-substituted C 1 ~C 6 Alkylene divalent radical, dihydroxyl or dimethoxy-substituted C 2 ~C 6 an alkylene divalent radical, -C 2 H 4 -(O-C 2 H 4 ) m2 -divalent radical, -Z 4 -S-S-Z 4 -divalent radical, hydroxyl- or methoxy-substituted C 1 ~C 6 an alkylene divalent radical or a substituted or unsubstituted phenylene divalent radical, Z 3 is (a)-NR n3 -, (b) 【number】 , (c) -NR 0 -Z 5 -NR 0 -, and (d) -O-Z 6 is any one of the divalent radicals —O—, Z 4 is C 1 ~C 6 is an alkylene divalent radical, Z 5 is C 1 ~C 6 an alkylene divalent radical, a 2-hydroxylpropylene divalent radical, a 2-(phosphonyloxy)propylene divalent radical, a 1,2-dihydroxyethylene divalent radical, or a 2,3-dihydroxybutylene divalent radical, Z 6 (a) C 1 ~C 6 an alkylene divalent radical; (b) 【number】 or (c) a substituted C having a hydroxyl group or a phosphonyloxy group. 3 ~C 8 is an alkylene divalent radical, Z 7 teeth, 【number】 is a divalent radical of The method of claim 10, further comprising the step of:
13. The silicone hydrogel material comprises repeat units of at least one polysiloxane vinyl crosslinker, the at least one polysiloxane vinyl crosslinker being selected from the group consisting of α,ω-bis[3-(meth)acrylamidopropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxy-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxyeth ... α,ω-bis[3-(meth)acryloxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxypropyloxy-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxy-isopropyloxy-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxybutyloxy-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxybutyloxy-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, midoethoxy-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamidepropyloxy-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamideisopropyloxy-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamidebutyloxy-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3- (meth)acryloxyethylamino-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxypropylamino-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acryloxybutylamino-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[(meth)acrylamideethylamino-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamidepropylamino-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[3-(meth)acrylamide-butylamino-2-hydroxypropyloxypropyl]-terminated polydimethylsiloxane, α,ω-bis[(meth)acryloxy-2-hydroxypropyloxy-ethoxypropyl]-terminated polydimethylsiloxane, α,ω-bis[(meth)acryloxy-2-hydroxypropyl-N-ethylaminopropyl]-terminated polydimethylsiloxane, α,ω-bis[(meth)acryloxy 11. The method of claim 10, wherein the polydimethylsiloxane is selected from the group consisting of α,ω-bis[(meth)acryloxy-2-hydroxypropyl-aminopropyl]-polydimethylsiloxane, α,ω-bis[(meth)acryloxy-2-hydroxypropyloxy-(polyethyleneoxy)propyl]-terminated polydimethylsiloxane, α,ω-bis[(meth)acryloxyethylamino-carbonyloxy-ethoxypropyl]-terminated polydimethylsiloxane, α,ω-bis[(meth)acryloxyethylamino-carbonyloxy-(polyethyleneoxy)propyl]-terminated polydimethylsiloxane, or combinations thereof.
14. The at least one hydrophilic vinyl monomer is (1) an alkyl(meth)acrylamide selected from the group consisting of (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-3-methoxypropyl(meth)acrylamide, and combinations thereof; (2) an alkyl(meth)acrylamide selected from the group consisting of N-2-hydroxyethyl(meth)acrylamide, N,N-bis(hydroxyethyl)(meth)acrylamide, N-3-hydroxypropyl(meth)acrylamide, N-2-hydroxypropyl(meth)acrylamide, N-2,3-dihydroxypropyl(meth)acrylamide, N-tris(hydroxymethyl)methyl(meth)acrylamide, 2-hydroxyethyl(meth)acrylate, 3-hydroxypropyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, glycerol methacrylate (GMA), di(ethylene glycol (3) a hydroxyl-containing acrylic monomer selected from the group consisting of 2-(meth)acrylamidoglycolic acid, (meth)acrylic acid, ethylacrylic acid, 3-(meth)acrylamidopropionic acid, 5-(meth)acrylamidopentanoic acid, 4-(meth)acrylamidobutanoic acid, 3-(meth)acrylamido-2-methylbutanoic acid, 3-(meth)acrylamido-3-methylbutanoic acid, 2-(meth)acrylamido-2-methyl-3,3-dimethylbutanoic acid, 3-(meth)acrylamidohexanoic acid, 4-(meth)acrylamido-3,3-dimethylhexanoic acid, and combinations thereof;(4) Amino-containing acrylic monomers selected from the group consisting of N-2-aminoethyl(meth)acrylamide, N-2-methylaminoethyl(meth)acrylamide, N-2-ethylaminoethyl(meth)acrylamide, N-2-dimethylaminoethyl(meth)acrylamide, N-3-aminopropyl(meth)acrylamide, N-3-methylaminopropyl(meth)acrylamide, N-3-dimethylaminopropyl(meth)acrylamide, 2-aminoethyl(meth)acrylate, 2-methylaminoethyl(meth)acrylate, 2-ethylaminoethyl(meth)acrylate, 3-aminopropyl(meth)acrylate, 3-methylaminopropyl(meth)acrylate, 3-ethylaminopropyl(meth)acrylate, 3-amino-2-hydroxypropyl(meth)acrylate, trimethylammonium 2-hydroxypropyl(meth)acrylate hydrochloride, dimethylaminoethyl(meth)acrylate, and combinations thereof;(5) N-vinylpyrrolidone (also known as N-vinyl-2-pyrrolidone), N-vinyl-3-methyl-2-pyrrolidone, N-vinyl-4-methyl-2-pyrrolidone, N-vinyl-5-methyl-2-pyrrolidone, N-vinyl-6-methyl-2-pyrrolidone, N-vinyl-3-ethyl-2-pyrrolidone, N-vinyl-4,5-dimethyl-2-pyrrolidone, N-vinyl-5,5-dimethyl-2-pyrrolidone, N-vinyl-3,3,5-trimethyl-2-pyrrolidone, N-vinylpiperidone (also known as N-vinyl-2-piperidone), N-vinyl-3-methyl-2-piperidone, N-vinyl-4-methyl-2-piperidone, N-vinyl-5-methyl-2-piperidone, N-vinyl-6-methyl-2-piperidone, N-vinyl-6-ethyl-2-piperidone, N-vinyl-3,5-dimethyl-2-piperidone N-vinyl amide monomers selected from the group consisting of N-vinyl caprolactam, N-vinyl-4,4-dimethyl-2-piperidone, N-vinyl caprolactam (also known as N-vinyl-2-caprolactam), N-vinyl-3-methyl-2-caprolactam, N-vinyl-4-methyl-2-caprolactam, N-vinyl-7-methyl-2-caprolactam, N-vinyl-7-ethyl-2-caprolactam, N-vinyl-3,5-dimethyl-2-caprolactam, N-vinyl-4,6-dimethyl-2-caprolactam, N-vinyl-3,5,7-trimethyl-2-caprolactam, N-vinyl-N-methylacetamide, N-vinylformamide, N-vinylacetamide, N-vinylisopropylamide, N-vinyl-N-ethylacetamide, N-vinyl-N-ethylformamide, and mixtures thereof;(6) methylene-containing pyrrolidone monomers selected from the group consisting of 1-methyl-3-methylene-2-pyrrolidone, 1-ethyl-3-methylene-2-pyrrolidone, 1-methyl-5-methylene-2-pyrrolidone, 1-ethyl-5-methylene-2-pyrrolidone, 5-methyl-3-methylene-2-pyrrolidone, 5-ethyl-3-methylene-2-pyrrolidone, 1-n-propyl-3-methylene-2-pyrrolidone, 1-n-propyl-5-methylene-2-pyrrolidone, 1-isopropyl-3-methylene-2-pyrrolidone, 1-isopropyl-5-methylene-2-pyrrolidone, 1-n-butyl-3-methylene-2-pyrrolidone, 1-tert-butyl-3-methylene-2-pyrrolidone, and combinations thereof; (7) C; 1 ~C 4 C having an alkoxyethoxy group and a number average molecular weight of up to 1500, such as ethylene glycol methyl ether (meth)acrylate, di(ethylene glycol) methyl ether (meth)acrylate, tri(ethylene glycol) methyl ether (meth)acrylate, tetra(ethylene glycol) methyl ether (meth)acrylate, 1 ~C 4 - alkoxy poly (ethylene glycol) (meth) acrylate, methoxy-poly (ethylene glycol) ethyl (meth) acrylamide having a number average molecular weight of up to 1500, and combinations thereof; (8) vinyl ether monomers selected from the group consisting of ethylene glycol monovinyl ether, di (ethylene glycol) monovinyl ether, tri (ethylene glycol) monovinyl ether, tetra (ethylene glycol) monovinyl ether, poly (ethylene glycol) monovinyl ether, ethylene glycol methyl vinyl ether, di (ethylene glycol) methyl vinyl ether, tri (ethylene glycol) methyl vinyl ether, tetra (ethylene glycol) methyl vinyl ether, poly (ethylene glycol) methyl vinyl ether, and combinations thereof; (9) ethylene glycol monoallyl ether, di (ethylene glycol) monoallyl ether, tri (ethylene glycol) monoallyl ether, tetra (ethylene glycol) monoallyl ether, poly (ethylene glycol) monoallyl ether (10) allyl ether monomers selected from the group consisting of (meth)acryloyloxyethyl phosphorylcholine, (meth)acryloyloxypropyl phosphorylcholine, 4-((meth)acryloyloxy)butyl-2'-(trimethylammonio) ethyl phosphate, 2-[(meth)acryloylamino]ethyl-2'-(trimethylammonio)-ethyl phosphate, 3-[(meth)acryloylamino]propyl-2'-(trimethylammonio)ethyl phosphate, 4-[(meth)acryloylamino]butyl-2'-(trimethylammonio)ethyl phosphate, 5-((meth)acryloyloxy)pentyl-2'-(trimethylammonio)ethyl phosphate, 6-((meth)acryloyloxy)hexyl-2'-(trimethylammonio)-ethyl phosphate,2-((meth)acryloyloxy)ethyl-2'-(triethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl-2'-(tripropylammonio)ethyl phosphate, 2-((meth)acryloyloxy)ethyl-2'-(tributylammonio)ethyl phosphate, 2-((meth)acryloyloxy)propyl-2'-(trimethylammonio)-ethyl phosphate, 2-((meth)acryloyloxy)ethyl-2'-(triethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)butyl-2'-(trimethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)pentyl-2'-(trimethylammonio)ethyl phosphate, 2-((meth)acryloyloxy)hexyl-2'-(trimethylammonio)ethyl phosphate, 2-(vinyloxy)ethyl-2'-(trimethylammonio)ethyl phosphate, 2-(allyloxy)ethyl-2'-(trimethylammonio)ethyl phosphate 14. The method of any one of claims 10 to 13, comprising a phosphorylcholine-containing vinyl monomer selected from the group consisting of phosphorylcholine-containing vinyl monomers ...
15. 15. The method of any one of claims 11 to 14, wherein the silicone hydrogel material comprises (a) repeat units of at least one non-silicone vinyl crosslinker, (b) repeat units of at least one blended vinyl monomer, and / or (c) repeat units of at least one UV absorbing vinyl monomer and / or at least one UV / HEVL absorbing vinyl monomer.
16. 16. The method of any one of claims 1 to 15, wherein the static water contact angle of the ready-to-use silicone hydrogel contact lens directly removed from the sealed, autoclaved package is at least 10° less than the static water contact angle of the preformed silicone hydrogel contact lens.
17. 17. The method of any one of claims 1 to 16, wherein the pre-autoclaved packaging solution comprises 0.010% to 0.030% by weight of the polymeric surfactant.
18. The method according to any one of claims 1 to 17, wherein the polymeric surfactant has a number average molecular weight of 800 to 10,000 Daltons.
19. The method according to any one of claims 1 to 17, wherein the polymeric surfactant has a number average molecular weight of 1,000 to 8,000 Daltons.
20. The method of any one of claims 1 to 19, wherein the sealed package is autoclaved for at least 45 minutes.
Citation Information
Patent Citations
Use of PEO-PBO block copolymers in ophthalmic compositions
JP2013065026A
Contact Lens Packaging Solution
JP2019507908A
Polymerizable polydimethylsiloxane-polyoxyalkylene block copolymer
JP2019531515A
Silicone hydrogel contact lenses
US20180355112A1